Artificial intelligence-assisted phenotypic monitoring and diagnostic of wastewater microbiome management towards sustainability - Zijian Wang; Yuan Yan; IL Han; Jangho Lee; Guangyu Li; Peisheng He; Annalisa Onnis-Hayden; Nicholas B. Tooker; Zijun Meng; Mark Wallace Miller; Kester McCullough; Stephanie Klaus; et al. (Water Research, 2026)

Genomic and food-safety evaluation of Staphylococcus chromogenes in Chinese dairy milk - Xiaoping Li; Baoling Zhang; Tao Zhou; Moli Li; Kai Chen; Shu Li; Xiaofang Tong; Herman W. Barkema; Diego B. Nobrega; John P. Kastelic; Yuqiong Li; A Yao; et al. (Food Research International, 2026)

Clinical outcomes of patients with brain metastases from primary esophageal cancer - Bianca Nolde-Lopez; Christina K. Cramer; Scott Isom; Anthony Naquin; Caio M.S.P. Rocha Lima; Ravi K. Paluri; Jimmy Ruiz; Fei Xing; Christopher T. Whitlow; Stephen B. Tatter; Adrian W. Laxton; Jaclyn J. White; et al. (Next Research, 2026)

Investigation of force-transfer mechanisms in reinforced concrete walls with construction joints using high-fidelity simulations - Terry Y.P. Yuen; Min-Yuan Cheng; Tzu-Han Wen; Marnie B. Giduquio (Engineering Structures, 2026)

Detection of seizurogenic compounds in human and rat neurons in vitro: A multi-laboratory, multi-model assessment - Ruth Roberts; Ksenia Blinova; Coby Carlson; Matthew Cato; Katherine Czysz; Tromondae K. Feaster; Xiaobo Han; Yuto Ishibashi; Yasunari Kanda; Mohamed Kreir; Paul Levesque; Norimasa Miyamoto; et al. (NeuroToxicology, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Phosphate-solubilizing bacteria-loaded biochar alleviates microplastic–cadmium co-contamination by reshaping the soil phosphorus cycling network - Meng Wang; Yan Chen; Yue-Liang Meng; Shan-Shan Gao; B. Larry Li; Yu-Ying Li; Xue-Min Ren; Hui Han; Ling Liu; Zhao-Jin Chen (Journal of Environmental Chemical Engineering, 2026)

Eight recommendations to enhance biodiversity outcomes of nature-based solutions at multiple scales - Charles B. van Rees; Collin VanBuren; Lori A. Han; Andrew Altieri; Matt Bilskie; James E. Byers; Jon Calabria; Matthew L. Chambers; Daniel J. Coleman; Katie Foster; Aliza Leit; Alec Nelson; et al. (Journal of Environmental Management, 2026)

Behavioural thermoregulation segregates sick and healthy fish to enable selective treatment - Massiel F. Copara Chino; Jayoon Lee; Yujin Han; Julia G. Neyedly; Matthew L. Michnik; Patrick Whittaker; Kathryn Smith; Keith B. Tierney; Yamila Carpio; Mario P. Estrada; Mark D. Fast; Brian Dixon; et al. (Aquaculture, 2026)

Extraction and characterization of bioactive oligosaccharides from pulse processing byproducts using subcritical water extraction: a proof-of-concept study - Jasmin S. Yang; T. Truc K. Pham; Andrea J.C. Tam; Han Peng; Tássia B. Pessato; You-Tae Kim; Peter J. Russell; Zhiliang Fan; David A. Mills; Daniela Barile; Juliana Maria Leite Nobrega de Moura Bell (Food Chemistry, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Unified prediction equation for equilibrium scour depth around vibrating monopile foundations - Zishun Yao; Han Wang; Bruce Melville; B. Mutlu Sumer; Dawei Guan (Coastal Engineering, 2026)

Mosquito-borne disease among individuals experiencing homelessness in the USA: a literature review - André B. B. Wilke; Megan D. Hill; Allisandra G. Kummer; Chalmers Vasquez; John-Paul Mutebi; Xi Huo; Han Li; Jing Chen; Shigui Ruan; John C. Beier; Maria Litvinova; Thomas Byrne; et al. (Journal of Pest Science, 2026)
Mosquito-borne diseases are a major public health issue. The USA has experienced mosquito-borne disease outbreaks, including West Nile virus, Zika, dengue, and malaria, highlighting widespread risk across the country. In the USA, exposure to mosquito vectors primarily occurs outdoors. Individuals experiencing unsheltered homelessness are particularly vulnerable to mosquito-borne diseases due to their increased exposure to mosquito vectors, limited access to healthcare, and high prevalence of underlying conditions. This review aims to examine the literature on mosquito-borne disease infections among individuals experiencing homelessness in the USA between 1999 and 2024. Our search strategy used Boolean methods on PubMed, Scopus, and Web of Science to select relevant publications. Two queries were used: the first query focused on individuals experiencing homelessness and mosquito-borne diseases, and the second one focused on epidemiological analyses of mosquito-borne disease outbreaks in the USA. Only studies reporting at least one infection among individuals experiencing homelessness were included. Our search resulted in the identification of 347 studies. After screening them, eight were ultimately included in this review. Half of the studies identified West Nile virus among individuals experiencing homelessness, and the other half reported cases of malaria. These studies show that individuals who spend more time outdoors, including individuals experiencing homelessness, may be at a greater risk of MBDs compared to the general population. However, the full extent of mosquito-borne disease exposure among individuals experiencing homelessness remains unclear. With climate change and globalization, there is a consensus in the literature showing an increasing risk of mosquito-borne disease transmission in the next decades, and we have already started to witness this increasing trend. Moreover, the USA is experiencing a steep increase in the overall nationwide homeless population. Therefore, we argue that developing policies aimed at providing homeless populations with housing during mosquito-borne disease outbreaks could be instrumental in protecting this segment of the population and promoting health equity.

Dose-dependent cerebral metabolic impairment in a swine model of carbon monoxide poisoning - Alistair Lewis; Rodrigo M. Forti; Tiffany S. Ko; John C. Greenwood; Matthew Kelly; Frances S. Shofer; Shih-Han Kao; Samuel S. Shin; Devesh Bungatavula; Mckenna Mason; Jonathan Starr; Johannes K. Ehinger; et al. (NeuroToxicology, 2026)

Efficient removal of ibuprofen and ketoprofen from aqueous solutions using ZIF-8: A comparative study of two synthesis technique - Jinyang Han; Ahmad B. Albadarin; Chenxi Guo; Titao Fang; Hanjing Wei; Chirangano Mangwandi; Bingmeng Hu (Journal of Cleaner Production, 2026)

Grain-size-specific Sr–Nd isotopic evidence for the dominant role of fluvial sediments in Danube loess formation - Xuechao Wu; Qingzhen Hao; Slobodan B. Marković; Xinbo Gao; Long Han; Yu Fu; Yang Song; Zhipeng Wu; Shouye Yang; Zhengtang Guo (Geochimica et Cosmochimica Acta, 2026)

Synergistic effect of β-cyclodextrin-functionalized biochar -based bacterial agent on soil lead/cadmium passivation and plant growth promotion - Jianbang Zhu; Qiwen An; Mengning Wang; Irina B. Ivshina; Xu Sun; Jiaqi Liu; Bohao Jing; Yongtao Zhou; Siyue Han; Jianhua Qu; Ying Zhang (Chemical Engineering Journal, 2026)

Non‐Correlated Variation of Leaf and Fine Root Traits in Subtropical Forest Plants - Yuzhi Zhu; Meng Li; Junyong Zheng; Yongqiang Wang; Yanghang Ren; Han Zhang; Zeyu Feng; Sandy P. Harrison; I. Colin Prentice; Yue Zhang; Lewei Jin; Shuang Sun; et al. (Ecology Letters, 2026)
Plants employ multiple strategies to adapt to their growth environment. Characterizing key dimensions in plant trait space is important for understanding functional diversity within ecosystems. Leaf and root functional traits have been studied in the context of resource economics, but whether they covary, and through which mechanisms, is still debated. We investigated this in subtropical forests by sampling root and leaf traits on individuals of co‐existing species in two communities with different resource availability. We found largely non‐correlated variation between leaf and fine root traits both across and within communities, and a clear decoupling between leaf economic spectrum and root economic space, independent of evolutionary history. Our results suggest that leaf‐root trait relationships are shaped by an interplay between microenvironmental heterogeneity that drives decoupling and shared selection pressures promoting covariation. The interplay explains the weak observed coordination and highlights the importance of environmental context in predicting above‐ and below‐ground plant functions.

Active immunization against myostatin and activin A improves skeletal muscle performance in growth hormone-deficient mice - Mishfak A. M. Mansoor; Sarah A. Ashiqueali; Md Tanjim Alam; Fabrizzio Lijeron-Herrera; Xiang Zhu; Jash Trivedi; Amanda Lasseter; Augusto Schneider; Lisa Flores; Hu Wang; Xianlin Han; Yuji Ikeno; et al. (GeroScience, 2026)

Astaxanthin, meclizine, mitoglitazone, pioglitazone, alpha-ketoglutarate, mifepristone, methotrexate, and atorvastatin-telmisartan do not increase lifespan in UM-HET3 mice - Ron Korstanje; Randy Strong; Adam B. Salmon; Molly A. Bogue; Sean P. Curran; Vivian Diaz; Elizabeth Fernandez; Brett Ginsburg; Melissa Han; David E. Harrison; Catherine Kaczorowski; Matt Kaeberlein; et al. (GeroScience, 2026)

Ba isotope unmasks recycling processes of fluid mobile elements in subduction zones - Yang Yu; Xiao-Long Huang; Betchaida D. Payot; Hai-Quan Liu; Ying-De Jiang; Yu Wang; Carla B. Dimalanta; Xin-Feng Ou; Gabriel Theophilus V. Valera; Fan Yang; Graciano P. Yumul; Yi-Gang Xu; et al. (Geochimica et Cosmochimica Acta, 2026)

Earthworms Enhance Global Soil Carbon Storage Through Microbial–Mineral Stabilization - Yuanyuan Li; Jiahui Liao; Peter B. Reich; Yu Fang; Jiajie Cao; Juanping Ni; Tingting Ren; Guobing Wang; Xiaoming Zou; Honghua Ruan; Han Y. H. Chen (Global Change Biology, 2026)
Earthworms play a dual role in the global carbon cycle: they accelerate organic matter decomposition yet are often associated with greater soil organic carbon (SOC) storage. However, uncertainty regarding the mechanisms and magnitudes through which earthworms concurrently influence SOC mineralization and stabilization has limited the integration of soil fauna into carbon models. Here, we synthesize 696 paired observations from 122 studies worldwide to resolve this uncertainty. On average, earthworms increase SOC by 5.4% (95% CI: 2.2%–9.1%), with effects strengthening over time under sustained plant‐derived carbon inputs. Earthworms enhance mineral‐associated organic carbon (MAOC) by 21.2%, while particulate organic carbon (POC) remains unchanged. These patterns suggest that earthworm activity promotes a transition from short‐term carbon mineralization to long‐term stabilization, likely mediated by the coupling of microbial processing and physical protection. Specifically, epigeic earthworms boost microbial biomass carbon, whereas endogeic species enhance macroaggregate formation, facilitating the incorporation of microbial necromass into MAOC. The magnitude and direction of these effects depend on sustained carbon inputs and earthworm functional type. Collectively, these results reconcile decades of conflicting evidence and provide the first quantitative global synthesis showing that earthworms increased soil carbon over time under sustained plant carbon inputs. This microbial–mineral formation pathway has direct implications for climate‐smart land management, soil biodiversity conservation, and the representation of earthworm bioturbation in global carbon models.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Comparison of metabolomic and transcriptomic analyses of Ganping mandarin fruit following on tree storage and postharvest low temperature storage - Xinyu Huang; Luoao Lin; John B. Golding; Penta Pristijono; Su Guo; Youjian Yu; Gang Chen; Dongdao Han; Huqing Yang; Ruihua Bai; Yongxin Li (Postharvest Biology and Technology, 2026)

Exploring causal pathways among soil moisture, climate and ocean–atmosphere teleconnection patterns over the drought-prone Greater Horn of Africa - Wen Zhuo; Shibo Fang; Xinran Gao; Ricardo B. Lourenço; Yanru Yu; Jiahao Han; Alemu Gonsamo (Journal of Hydrology, 2026)

Late Pliocene-Quaternary climate-environment evolution on the southeastern Tibetan Plateau and links to hominin dynamics - Yidan Long; Wenxia Han; Boyan Sun; Yifei Fan; Xue Xiao; Tianli Wang; David B. Kemp; Chenyu Shang; Yunping Chi; Xiaomin Fang (CATENA, 2026)

The analysis of road stormwater runoff pollution in the typical coastal city of Lianyungang, East China - H. Leng; H. Luo; R. Han; W. Wu; B. Song; Y. Zhao; B.-J. He (International Journal of Environmental Science and Technology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Late Eocene periodic precipitation increases and evaporite deposition on the Tibetan Plateau forced by proto-Paratethys incursions - Wenxia Han; Tianli Wang; Qian Tian; David B. Kemp; Tao Zhang; Boyan Sun; Zhixiang Wang; Li Mai; Xiaomin Fang (Global and Planetary Change, 2025)

Polymer nanocomposites for the environmental remediation of contaminated water bodies - T.V. Surendra; Chandra Sekhar Espenti; B. Srinivas; Kummara Madhusudana Rao; K.S.V. Krishna Rao; Sung Soo Han (Journal of Environmental Chemical Engineering, 2025)

Nutrient cycles in transition: C:N:P stoichiometry by forest conversion to plantations - Ying Wang; Anna Gunina; Peter B. Reich; Defeng Yang; Han Y.H. Chen; Yakov Kuzyakov; Yongxing Cui; Jingwen Chen; Zhiming Guo; Tao Sun (Forest Ecology and Management, 2025)

Strongest untreated mycelium materials produced by Schizophyllum commune dikaryons - Antonio d’Errico; Jeroen G. van den Brandhof; Anna Bogomolova; Han A. B. Wösten (World Journal of Microbiology and Biotechnology, 2025)
Monokaryons of Schizophyllum commune are preferred to produce mycelium materials due to their inability to form fruiting bodies and thereby producing uniform materials. However, a single gene mutation in such monokaryons can negatively impact biomass, chemical composition, and mechanical properties of the mycelium material. Dikaryons contain two instead of a single nucleus per hyphal compartment, thereby promoting higher phenotypic stability in the case of recessive mutations. Here, biomass formation and mycelium material properties of four S. commune dikaryons were compared to a monokaryon commonly used in mycelium material production. To this end, mycelium was grown in three different growth media. The monokaryon yielded a biomass of 3.11–9.31 g L −1 , an ultimate tensile strength ( σ ) of 4.62–7.77 MPa, a Young’s modulus ( E ) of 0.38–0.64 GPa, and an elongation at break ( ε ) of 1.51–1.93%. Most dikaryons exhibited a strikingly higher σ (19.55–47.29 MPa), a similar or higher E (0.69–2.06 GPa) and ε (2.09–7.92%), and a lower or similar biomass (1.48–7.71 g L −1 ). Notably, σ values up to 47.29 and 47.16 MPa were obtained for the diakaryotic S. commune strains 139 and 351, respectively, making them the strongest untreated mycelium materials reported so far. Results suggest that this high strength is caused, at least in part, by a high amount of KOH-soluble cell wall components and by low sc3 expression.

Extension of lifespan by epicatechin, halofuginone and mitoglitazone in male but not female genetically heterogeneous mice - Randy Strong; James F. Nelson; Molly A. Bogue; Jerry R. Colca; Martin Denzel; Vivian Diaz; Brian N. Finck; Vadim N. Gladyshev; Steve Horvath; Nisi Jiang; Tracy Keller; Rolf F. Kletzien; et al. (GeroScience, 2025)
Mice bred in 2021 were tested by the Interventions Testing Program (ITP) for possible lifespan benefits of 2BAct (2BA), dichloroacetate (DCA), Epicatechin (EPI), Forskolin (FSK), Halofuginone (HAL) and Mitoglitazone (MIT). All agents were administered in the diet ad libitum beginning at 7 months of age. In male mice, EPI increased median lifespan by ~ 5%, and HAL and MIT each increased median lifespan by ~ 9%. EPI and HAL, but not MIT, increased 90% survival. In addition to adding 3 new agents to the list of interventions identified by the ITP that extend lifespan, this report continues the strong male bias in the efficacy of life-extending drugs identified so far.

Utilization of oxided tamarind polysaccharide gum as novel selective depressant in the flotation separation of copper-lead-zinc sulfide ore - Tichen Wang; Jiushuai Deng; Hao Zhang; Dingquan Xing; Zhiguo Han; Jie Sheng; Chul B. Park (Process Safety and Environmental Protection, 2025)

Oxidative modification and structural characterization of konjac gum and its effect on the flotation separation of chalcopyrite from galena - Tichen Wang; Jiushuai Deng; Dingquan Xing; Zhiguo Han; Yue Gao; Qizheng Qin; Hao Zhang; Hongxiang Xu; Chul B. Park (Journal of Cleaner Production, 2025)

Dual-defect engineering strategy induced polarization loss in trimetallic MOFs/MXene-derived nanocomposites for broadening microwave absorption bandwidth - Yuanzhao Hou; Binchuan Li; Kuiren Liu; Jianshe Chen; Yongfeng Chang; Bo Wang; Shicheng Wei; Xiaocai He; Da Li; Chul B. Park; Daxue Fu; Qing Han (Chemical Engineering Journal, 2025)

Characterization of pure mycelium materials from different mushroom-forming fungi - Jeroen G. van den Brandhof; Noortje Hansen; Chen Hou; Sander C. Broers; Martin Tegelaar; Han A. B. Wösten (Antonie van Leeuwenhoek, 2025)
Pure mycelium materials (PMMs) are a sustainable alternative for a range of non-sustainable products such as textile, leather and meat. So far, properties of PMMs of different fungi have not been systematically assessed. Here, 11 mushroom-forming fungi, of which 10 isolated from nature, were grown in liquid shaken cultures. Schizophyllum commune, Ganoderma resinaceum , and Trametes betulina produced the highest biomass (8.62, 7.58, and 6.94 g L −1 , respectively) when grown as mono-cultures in malt extract broth. Therefore, PMM properties were determined of mono-cultures, mixed-cultures, and co-cultures of these three fungi. The maximum tensile strength of the PMMs of the mono-cultures, mixed-cultures, and co-cultures of S. commune , G. resinaceum , and T. betulina did not show significant differences and ranged between 4.5 to 6.3 MPa. The elongation at break of the different PMMs was generally low and ranged between 0.8 and 1.6%. The Young’s modulus of the PMMs also showed relatively small differences ranging between 408 and 710 MPa. The G. resinaceum PMMs showed the lowest water uptake, while the S. commune mono-, mixed- and co-culture PMMs showed the highest water contact angle. Together, it is concluded that the properties of the mono-, mixed-, and co-cultures of S. commune , G. resinaceum , and T. betulina are not very different. These data suggest that the species of mushroom forming fungi does not have a major impact on PMM properties of biomass from liquid shaken cultures.

Development of a non-deterministic fractional low-carbon transition programming method associated with Sustainable Development Goals (SDGs) assessment--application to Shanxi Province, China - Y.L. Zheng; G.H. Huang; Y.P. Li; D.C. Han; B. Luo; R.J. Hao; W.C. Tang (Journal of Cleaner Production, 2025)

Association of urinary phthalate metabolite concentrations with inflammatory biomarker levels among pregnant women - Han Han; Sarah Grill; Xilin Shen; Paige L. Williams; Tamarra James-Todd; Jennifer B. Ford; Kathryn M. Rexrode; Antonia M. Calafat; Jorge E. Chavarro; Russ Hauser; Lidia Mínguez-Alarcón (Environmental Research, 2025)

Evidence for elevated wildfire activity during Cretaceous OAE 2 from eastern Tethys - Shuai Shi; Xi Chen; Huifang Guo; Hanwei Yao; Kaibo Han; David B. Kemp; Shengbao Shi; Zhong Han; Chengshan Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Corrigendum to “High-resolution organic carbon isotope chemostratigraphy of the lower Aptian and the expression of Oceanic Anoxic Event 1a in the Tibetan Himalaya” [Global and Planetary Change 248C (2025), 104759] - Kaibo Han; Zhiqin Liu; Xi Chen; Xuan Liu; Huifang Guo; Hanwei Yao; Yi Zhang; David B. Kemp; Chengshan Wang (Global and Planetary Change, 2025)

Alzheimer’s disease polygenic risk’s association with all-cause dementia through the plasma metabolome in the UK Biobank study - May A. Beydoun; Yi-Han Hu; Zhiguang Li; Michael F. Georgescu; Hind A. Beydoun; Nicole Noren Hooten; Keenan A. Walker; Mustapha Bouhrara; Lenore J. Launer; Michele K. Evans; Alan B. Zonderman (GeroScience, 2025)
Dementia, with Alzheimer’s Disease (AD) accounting for 60–70% of its occurrences, is a multifactorial disorder marked by cognitive and functional decline. Polygenic risk scores (PRS) stratify genetic risk for complex diseases, including AD. Integrating PRS with metabolomics offers a pathway to better understand AD etiology and identify biomarkers for early detection. We explored the association between AD PRS, metabolomics, and dementia risk using data from the UK Biobank. The analysis emphasizes sex-specific associations and the mediating role of metabolites between AD PRS and dementia risk. The study utilized data from 205,219 UK Biobank participants aged ≥ 50 years at baseline. Dementia outcomes were derived using ICD-10 codes. AD PRS were computed using genome-wide association study data, while metabolomic data included 249 biomarkers measured via Nuclear Magnetic Resonance. Time-to-event analyses (Cox proportional hazards models) and generalized structural equation modeling assessed associations and mediation effects, adjusting for age, sex, and genetic principal components. Higher AD PRS was associated with increased risks of all-cause dementia (HR: 1.75, 95% CI: 1.70–1.79, P < 0.001) and AD (HR: 2.02, 95% CI: 1.95–2.09, P < 0.001), with stronger effects in women for both outcomes when considering the main AD PRS which was related to APOE4 status. Metabolomic analyses identified lipid-related markers as key mediators. LDL phospholipid content was the metabolite marker with the strongest positive relationship with AD genetic risk (effect size, b = + 0.11), while HDL phospholipids percentage showed a similarly strong inverse association (effect size b = -0.09). No metabolomic markers were significantly associated with another version of AD PRS that was less correlated with APOE4 status. Mediation analyses applied to the main AD PRS revealed modest effects, with LDL-related metabolomic components partially mediating the effect of genetic risk on dementia incidence, through a protective type of mediation (< -2%). Nevertheless, most genetic risk operated independently of metabolites. AD PRS is significantly associated with dementia risk, with sex differences and metabolomic pathways providing further insights. Lipid metabolism, particularly LDL-centric measures, emerged as potential mediators. This integrative approach highlights the utility of combining genetic and metabolomic data to identify biomarkers and potential targets for early intervention in AD and dementia.

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16-hydroxyestradiol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2025)

Growth performance, swimming capacity, and fillet quality in rainbow trout fed a transgene-derived omega-3 and carotenoid-enriched oil - Pauline Wischhusen; Angelico Madaro; Malthe Hvas; Richard Broughton; Lihua Han; Karla Fernandez Quiroz; Kasidis Chaiyasut; Akhil Gupta; Rolf Erik Olsen; Stéphanie Fontagné-Dicharry; Johnathan A. Napier; Mónica B. Betancor (Aquaculture, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

High-resolution organic carbon isotope chemostratigraphy of the lower Aptian and the expression of Oceanic Anoxic Event 1a in the Tibetan Himalaya - Kaibo Han; Zhiqin Liu; Xi Chen; Xuan Liu; Huifang Guo; Hanwei Yao; Yi Zhang; David B. Kemp; Chengshan Wang (Global and Planetary Change, 2025)

Selective and sensitive Electrocatalytic behavior of hierarchical SnS decorated on La2Sn2O7 embedded carbon nanofibers for detection of antioxidant diphenylamine in fruits samples - Gagankumar Sakleshpur Kumar; Harshitha B. Tyagaraj; Ali Mohammadi; Shalmali R. Burse; Hyun Uk Lee; Kugalur Shanmugam Ranjith; Yun Suk Huh; Young-Kyu Han (Food Chemistry, 2025)

Paper-immobilized liquid-phase microextraction for direct paper spray mass spectrometry and immuno-detection of atropine in baby food, buckwheat cereals, and edible oils at regulatory levels - Ids B. Lemmink; Sipke J. Bosma; Toine F.H. Bovee; Han Zuilhof; Gert IJ. Salentijn (Analytica Chimica Acta, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Non-additive effects of leaf-litter flammability on eight subtropical tree species: Implications for forest species composition and fire susceptibility - Pujie Wei; Li Tang; Zixuan Xiong; Byron B. Lamont; Lin Chen; Weixing Xue; Zeyao Zhao; Wenxiong Lu; Jisi Han; Wanwan He; Wei Yang; Zhaogui Yan (Journal of Environmental Management, 2025)

Excitation functions for fast neutron induced reactions on Al, Zr, In and Au - B. Liu; G. Tian; R. Han; F. Shi; H. Sun; Z. Chen; Z. Zhang; Q. Li; P. Luo (Annals of Nuclear Energy, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Characterizing biomarkers of ageing in Singaporeans: the ABIOS observational study protocol - Jessica K. Lu; Weilan Wang; Janjira Soh; Elena Sandalova; Zhi Meng Lim; Santosh Kumar Seetharaman; Jing-Dong Jackie Han; Desmond B. Teo; Brian K. Kennedy; Jorming Goh; Andrea B. Maier (GeroScience, 2025)
Ageing is the primary driver of age-associated chronic diseases and conditions. Asian populations have traditionally been underrepresented in studies understanding age-related diseases. Thus, the Ageing BIOmarker Study in Singaporeans (ABIOS) aims to characterise biomarkers of ageing in Singaporeans, exploring associations between molecular, physiological, and digital biomarkers of ageing. This is a single-centre, cross-sectional study that recruits healthy community-dwelling adults (≥ 21 years) from three different ethnic groups (Chinese, Malay, and Indian). Molecular biomarkers of ageing include multi-omics approaches, such as DNA methylation analysis and metabolic and inflammatory proteomic profiling in blood, saliva, and stool. Physiological biomarkers of ageing include bone density, body composition, skin autofluorescence, arterial stiffness, physical performance (e.g., muscle strength and flexibility), cognition, and nutritional status. Digital biomarkers of ageing include three-dimensional facial morphology and objectively measured physical activity. Additional measures, such as habitual physical activity, dietary patterns, and medical history, are also examined. The associations between the molecular, physiological, and digital phenotypes will be explored. This study is expected to generate a comprehensive profile of molecular, physiological, and digital biomarkers of ageing in Chinese, Malay, and Indian populations in Singapore. By integrating diverse age-related biomarkers, clinical indicators, and lifestyle factors, ABIOS will offer unique insights into the ageing process specific to Southeast Asian populations. These findings can help identify markers of biological ageing, uncover ethnic-specific patterns, and reveal modifiable lifestyle factors for healthier ageing. The results could inform evidence-based health policies, personalized interventions, and future cross-ethnic comparative studies to enhance understanding of ageing biology across diverse populations.

A risk-based stochastic energy-water-carbon nexus analytical model to support provincial multi-system synergistic management – A case study of Shanxi, China - Y.L. Zheng; G.H. Huang; Y.P. Li; D.C. Han; B. Luo; Y.Y. Liu; W.C. Tang (Science of The Total Environment, 2024)

Multi-omics analysis of the effects of low-temperature storage on chilling injury of bitter gourd - Hongwei Wang; Ling Li; Da-Wen Sun; Lili Ma; Lichun Han; Xuelian He; Qing Wang; Christopher B. Watkins; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Editorial preface to special issue: Response of marine and terrestrial environments to Triassic–Paleogene hyperthermals - Zhong Han; Santanu Banerjee; Jacopo Dal Corso; Xiumian Hu; David B. Kemp (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Low storage temperature affects quality and volatile compounds in fresh tomatoes - Jiejie Tao; Jinhua Zuo; Christopher B. Watkins; Chunmei Bai; Xuelian He; Shiyu Liu; Lichun Han; Xiaoyan Zhao; Ye Liu; Jian Li; Yanyan Zheng (Food Chemistry, 2024)

Kidney tissue loading reduces the critical cooling/warming rates of cryoprotective solutions - Zonghu Han; Lakshya Gangwar; Bat-Erdene Namsrai; Joseph S. Rao; Michael L. Etheridge; Jeunghwan Choi; Erik B. Finger; John C. Bischof (Cryobiology, 2024)

Kidney tissue loading reduces the critical cooling and warming rates of VS55 and VMP cryoprotective solutions - Zonghu Han; Lakshya Gangwar; Bat-Erdene Namsrai; Joseph Sushil Rao; Cameron Scheithauer; Michael L. Etheridge; Erik B. Finger; John C. Bischof; Jeunghwan Choi (Cryobiology, 2024)

The role of the Flb protein family in the life cycle of Aspergillus niger - Xiaoyi Chen; Juan P. Moran Torres; Han A. B. Wösten (Antonie van Leeuwenhoek, 2024)
Genes flbA-E are involved in sporulation and vegetative growth in Aspergillus nidulans. Inactivation of either of these genes results in a fluffy phenotype with delayed or even abolished sporulation. Previously, a non-sporulating phenotype was obtained by inactivating flbA in Aspergillus niger, which was accompanied by lysis, thinner cell walls, and an increased secretome complexity. Here, we further studied the role of the flb genes of A. niger . Strains Δ flbA, Δ flbB and Δ flbE showed increased biomass formation, while inactivation of flbA-D reduced, or even abolished, formation of conidia. Strain Δ flbA was more sensitive to H 2 O 2 , DTT, and the cell wall integrity stress compounds SDS and Congo Red (CR). Also, Δ flbC was more sensitive to SDS, while Δ flbB , Δ flbD , and Δ flbE were more sensitive to CR. On the other hand, inactivation of flbE increased resistance to H 2 O 2 . Enzyme secretion was impacted when the Δ flb strains were grown on xylose. Strain Δ flbE showed reduced xylanase, cellulase and amylase secretion. On the other hand, amylase secretion at the periphery of the Δ flbA colony was reduced but not in its center, while secretion of this enzyme was increased in the center of the Δ flbB colony but not at its periphery. Inactivation of flbC and flbD also impacted zonal cellulase and amylase activity. Together, the Flb protein family of A. niger function in biomass formation, sporulation, stress response, and protein secretion.

Alzheimer’s Disease polygenic risk, the plasma proteome, and dementia incidence among UK older adults - May A. Beydoun; Hind A. Beydoun; Zhiguang Li; Yi-Han Hu; Nicole Noren Hooten; Jun Ding; Sharmin Hossain; Christian A. Maino Vieytes; Lenore J. Launer; Michele K. Evans; Alan B. Zonderman (GeroScience, 2024)
Alzheimer’s Disease (AD) is a complex polygenic neurodegenerative disorder. Its genetic risk’s relationship with all-cause dementia may be influenced by the plasma proteome. Up to 40,139 UK Biobank participants aged ≥ 50y at baseline assessment (2006–2010) were followed-up for ≤ 15 y for dementia incidence. Plasma proteomics were performed on a sub-sample of UK Biobank participants ( k = 1,463 plasma proteins). AD polygenic risk scores (PRS) were used as the primary exposure and Cox proportional hazards models were conducted to examine the AD PRS-dementia relationship. A four-way decomposition model then partitioned the total effect (TE) of AD PRS on dementia into an effect due to mediation only, an effect due to interaction only, neither or both. The study found that AD PRS tertiles significantly increased the risk for all-cause dementia, particularly among women. The study specifically found that AD PRS was associated with a 79% higher risk for all-cause dementia for each unit increase (HR = 1.79, 95% CI: 1.70–1.87, P < 0.001). Eighty-six plasma proteins were significantly predicted by AD PRS, including a positive association with PLA2G7, BRK1, the glial acidic fibrillary protein (GFAP), neurofilament light chain (NfL), and negative with TREM2. Both GFAP and NfL significantly interacted synergistically with AD PRS to increase all-dementia risk (> 10% of TE is pure interaction), while GFAP was also an important consistent mediator in the AD PRS-dementia relationship. In summary, we detected significant interactions of NfL and GFAP with AD PRS, in relation to dementia incidence, suggesting potential for personalized dementia prevention and management.

Millennial-scale sedimentary evolution of carbonate platforms during the Permian–Triassic boundary hyperthermal event - Jiawei He; Xiumian Hu; Juan Li; David B. Kemp; Mingcai Hou; Zhong Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Heterogeneous marine response during the Toarcian Oceanic Anoxic Event (TOAE): The potential role of storminess - Yuzhu Ge; Zhong Han; Thomas J. Algeo; David B. Kemp; Luya Wu (Global and Planetary Change, 2024)

Global hydroclimate perturbations during the Toarcian oceanic anoxic event - David B. Kemp; Zhong Han; Xiumian Hu; Wenhan Chen; Simin Jin; Kentaro Izumi; Qing Yan; Viktória Baranyi; Xin Jin; Jacopo Dal Corso; Yuzhu Ge (Earth-Science Reviews, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Uncovering mediational pathways behind racial and socioeconomic disparities in brain volumes: insights from the UK Biobank study - May A. Beydoun; Hind A. Beydoun; Marie T. Fanelli-Kuczmarski; Yi-Han Hu; Danielle Shaked; Jordan Weiss; Shari R. Waldstein; Lenore J. Launer; Michele K. Evans; Alan B. Zonderman (GeroScience, 2024)
Mediation pathways explaining racial/ethnic and socioeconomic (SES) disparities in structural MRI markers of brain health remain underexplored. We examined racial/ethnic and SES disparities in sMRI markers and tested total, direct, and indirect effects through lifestyle, health-related, and cognition factors using a structural equations modeling approach among 36,184 UK Biobank participants aged 40–70 years at baseline assessment (47% men). Race (non-White vs. White) and lower SES-predicted poorer brain sMRI volumetric outcomes at follow-up, with racial/ethnic disparities in sMRI outcomes involving multiple pathways and SES playing a central role in those pathways. Mediational patterns differed across outcomes, with the SES-sMRI total effect being partially mediated for all outcomes. Over 20% of the total effect (TE) of race/ethnicity on WMH was explained by the indirect effect (IE), by a combination of different pathways going through SES, lifestyle, health-related, and cognition factors. This is in contrast to < 10% for total brain, gray matter (GM), white matter (WM), and frontal GM left/right. Another significant finding is that around 57% of the total effect for SES and the normalized white matter hyperintensity (WMH) was attributed to an indirect effect. This effect encompasses many pathways that involve lifestyle, health-related, and cognitive aspects. Aside from WMH, the percent of TE of SES mediated through various pathways ranged from ~ 5% for WM to > 15% up to 36% for most of the remaining sMRI outcomes, which are composed mainly of GM phenotypes. Race and SES were important determinants of brain volumetric outcomes, with partial mediation of racial/ethnic disparities through SES, lifestyle, health-related, and cognition factors.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Multiomics comprehensive analysis of pre-storage low-temperature on cowpea metabolism - Lichun Han; Zhengrong Wang; Qing Wang; Da-Wen Sun; Xuelian He; Hongwei Wang; Lili Ma; Chunmei Bai; Christopher B. Watkins; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Inclusion of oil from transgenic Camelina sativa in feed effectively supplies EPA and DHA to Atlantic salmon (Salmo salar) grown to market size in seawater pens - Douglas R. Tocher; Matthew Sprague; Lihua Han; Olga Sayanova; Fernando Norambuena; Johnathan A. Napier; Mónica B. Betancor (Food Chemistry, 2024)

Quantifying the pattern of organic carbon burial through Cretaceous Oceanic Anoxic Event 2 - Huifang Guo; Xi Chen; Hanwei Yao; Yinggang Zhang; Benjamin J.W. Mills; Kaibo Han; Shujuan Wu; Yida Yang; Zihao Wang; David B. Kemp (Earth-Science Reviews, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Evolutionary ecology of masting: mechanisms, models, and climate change - Michal Bogdziewicz; Dave Kelly; Davide Ascoli; Thomas Caignard; Francesco Chianucci; Elizabeth E. Crone; Emilie Fleurot; Jessie J. Foest; Georg Gratzer; Tomika Hagiwara; Qingmin Han; Valentin Journé; et al. (Trends in Ecology & Evolution, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Proximity Labelling Confirms the Involvement of Papain-Like Cysteine Proteases and Chaperones in Cyclotide Biosynthesis - Meng-Han Lee; Mark A. Jackson; Fabian B. H. Rehm; Deborah S. Barkauskas; Wing L. Ho; Kuok Yap; David J. Craik; Edward K. Gilding (Plant Molecular Biology Reporter, 2024)
Cyclotides are disulfide-rich insecticidal peptides from plants that harbour a cyclic cystine knot motif that imparts them with high stability. Like most ribosomally encoded peptides, cyclotides are produced as precursor proteins that are subsequently processed to maturity through proteolytic activity. Although the final maturation of the prototypic cyclotide kalata B1 (kB1) is known to involve asparaginyl endopeptidases, the role of the in planta folding machinery is less well characterized, as is also the case for in planta N-terminal processing enzyme(s). Here, we used proximity labelling to identify proteins involved in the biosynthesis of kB1 in both a cyclotide-bearing plant species, Petunia × hybrida [Regel], and in Nicotiana benthamiana [Domin] that does not naturally produce cyclotides. Together, several ER resident chaperones, protein disulfide isomerases, a papain-like cysteine protease, and an asparaginyl endopeptidase were identified in the kB1 interactome. We found that overexpression of the identified papain-like cysteine protease resulted in an improvement in the yield of cyclic kB1, while this was not the case for the overexpression of protein disulfide isomerases, despite their interaction being verified using bimolecular fluorescence complementation. Together, these results provide a significant advance in our understanding of the role of auxiliary biosynthetic elements for heterologous cyclotide production in plants.

Screening of plant growth-promoting rhizobacteria helps alleviate the joint toxicity of PVC+Cd pollution in sorghum plants - Yu Zhang; Si-Yu Zhao; Ruo-Han Zhang; B. Larry Li; Yu-Ying Li; Hui Han; Peng-Fei Duan; Zhao-Jin Chen (Environmental Pollution, 2024)

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16‑hydroxyestriol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Nisi Jiang; Catherine C. Kaczorowski; Navasuja Kumar; et al. (GeroScience, 2024)

Biological and genomic characterization of 4 novel bacteriophages isolated from sewage or the environment using non-aureus Staphylococci strains - Xiaoping Li; Baoling Zhang; Xiaofang Tong; Tao Zhou; Moli Li; Herman W. Barkema; Diego B. Nobrega; John P. Kastelic; Chuang Xu; Bo Han; Jian Gao (Veterinary Microbiology, 2024)

Lifespan effects in male UM-HET3 mice treated with sodium thiosulfate, 16-hydroxyestriol, and late-start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2024)

Piezocatalytic property of PVDF/Graphene self-assembling piezoelectric membrane for environmental remediation - Tsung-Han Huang; Franz Kenneth C. Espino; Xin-Yuan Tian; Januar Widakdo; Hannah Faye M. Austria; Owen Setiawan; Wei-Song Hung; Kristopher Ray S. Pamintuan; Rhoda B. Leron; Ching-Yuan Chang; Alvin R. Caparanga; Kueir-Rarn Lee; et al. (Chemical Engineering Journal, 2024)

Side-Stream Enhanced Biological Phosphorus Removal (S2EBPR) enables effective phosphorus removal in a pilot-scale A-B stage shortcut nitrogen removal system for mainstream municipal wastewater treatment - Dongqi Wang; Il Han; Kester McCullough; Stephanie Klaus; Jangho Lee; Varun Srinivasan; Guangyu Li; Zijian Leo Wang; Charles B. Bott; Jim McQuarrie; Beverley M. Stinson; Christine deBarbadillo; et al. (Water Research, 2024)

Unusual weakening trend of the East Asian winter monsoon during MIS 8 revealed by Chinese loess deposits and its implications for ice age dynamics - Qingzhen Hao; Shuzhen Peng; Xinbo Gao; Slobodan B. Marković; Sheng-Hua Li; Junjie Zhang; Fengjiang Li; Long Han; Yu Fu; Xuechao Wu; Luo Wang; Bing Xu; et al. (Global and Planetary Change, 2024)

Numerical-geostatistical-based approach to investigate the earth pressure evolution within the large grid wall foundation under adjacent surcharge loading - Marsheal Fisonga; Yongtao Hu; Shijie Han; Yongfeng Deng; Rennie B. Kaunda (Computers and Geotechnics, 2024)

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

Review of risk assessment for navigational safety and supported decisions in arctic waters - X. Yang; Z.Y. Lin; W.J. Zhang; S. Xu; M.Y. Zhang; Z.D. Wu; B. Han (Ocean & Coastal Management, 2024)

The regulatory mechanisms of delayed senescence of nitric oxide treatment of hyacinth beans - Lichun Han; Zhengrong Wang; Christopher B. Watkins; Lili Ma; Xuelian He; Chunmei Bai; Hongwei Wang; Qing Wang; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Model-guided design and optimization of CPA perfusion protocols for whole organ cryopreservation - Zonghu Han; Joseph S. Rao; Srivasupradha Ramesh; Jan Hergesell; Bat-Erdene Namsrai; Michael L. Etheridge; Erik B. Finger; John C. Bischof (Cryobiology, 2023)

SUCCESSFUL TRANSPLANT OF KIDNEYS AFTER VITRIFICATION AND NANOWARMING - Zonghu Han; Joseph S. Rao; Lakshya Gangwar; Bat-Erdene Namsrai; Jacqueline Pasek-Allen; Michael L. Etheridge; Erik B. Finger; John C. Bischof (Cryobiology, 2023)

Assessing cellular and organ-level health, viability, and function of vitrified kidneys and islets for transplantation - Joseph Sushil Rao; Zonghu Han; Li Zhan; Michael L. Ethridge; John C. Bischof; Erik B. Finger (Cryobiology, 2023)

Model-Guided Design and Optimization of CPA Perfusion Protocols for Whole Organ Cryopreservation - Zonghu Han; Joseph Sushil Rao; Srivasupradha Ramesh; Jan Hergesell; Bat-Erdene Namsrai; Michael L. Etheridge; Erik B. Finger; John C. Bischof (Annals of Biomedical Engineering, 2023)
Vitrification could enable long-term organ preservation, but only after loading high-concentration, potentially toxic cryoprotective agents (CPAs) by perfusion. In this paper, we combine a two-compartment Krogh cylinder model with a toxicity cost function to theoretically optimize the loading of CPA (VMP) in rat kidneys as a model system. First, based on kidney perfusion experiments, we systematically derived the parameters for a CPA transport loading model, including the following: V b = 86.0% ( r a = 3.86 μm), L p = 1.5 × 10 –14 m 3 /(N·s), ω = 7.0 × 10 –13 mol/(N·s), σ = 0.10. Next, we measured the toxicity cost function model parameters as α = 3.12 and β = 9.39 × 10 –6 . Combining these models, we developed an improved kidney-loading protocol predicted to achieve vitrification while minimizing toxicity. The optimized protocol resulted in shorter exposure (25 min or 18.5% less) than the gold standard kidney-loading protocol for VMP, which had been developed based on decades of empirical practice. After testing both protocols on rat kidneys, we found comparable physical and biological outcomes. While we did not dramatically reduce toxicity, we did reduce the time. As our approach is now validated, it can be used on other organs lacking defined toxicity data to reduce CPA exposure time and provide a rapid path toward developing CPA perfusion protocols for other organs and CPAs.

P26-12: Acute and subacute toxicity profiles in Sprague-Dawley (SD) rats treated with Piperis Longi Fructus (PLF) aqueous extract - Y.-B. Kim; W.-J. Im; K.-H. Han (Toxicology Letters, 2023)

P26-11: Acute and subacute toxicity profiles in Sprague-Dawley (SD) rats treated with Piperis Longi Fructus (PLF) Powder - K.-H. Han; W.-J. Im; Y.-B. Kim (Toxicology Letters, 2023)

P19-07: 13-week repeated-dose oral toxicity study in rats treated with a mixture of Cirsium japonicum and Brassica oleracea extracts - W.-J. Im; M.-H. Yang; H. Park; J.-S. Han; J.-W. Cho; M.H. Yoo; Y.-B. Kim (Toxicology Letters, 2023)

Effect of fruiting-related genes on the formation of volatile organic compounds in the mushroom Schizophyllum commune - Axel Orban; Lisa Janaina Schwab; Luis G. Lugones; Han A. B. Wösten; Martin Rühl (Mycological Progress, 2023)
In fungi, little is known about connections between volatile organic compound (VOC) formation and developmental stages that are amongst others triggered by fruiting-related genes (FRGs). We analysed the volatilomes of Schizophyllum commune during different developmental stages in a variety of FRG-deletion strains and wild-type strains. The deletion strains Δ tea1 Δ tea1 , Δ wc-2 Δ wc-2 and Δ hom2 Δ hom2 were unable to develop fruiting bodies, and Δ fst4 Δ fst4 formed only rudimentary fruiting body structures. Early developmental stages of these strains were dominated by esters, including methyl 2-methylbutanoate, ethyl 2-methylbutanoate, isobutyl 2-methylpropionate, and 2-methylbutyl acetate, of which the last three were not found in the headspace (HS) of the wild-type samples. Compared to the wild type, in the HS of hom2 con samples, that are able to form fruiting bodies, methyl 2-methylbutanoate was the most abundant substance at early stages (68–81% of the total peak area). In contrast to fruiting body forming strains, Δ tea1 Δ tea1 , Δ wc-2 Δ wc-2 , Δ hom2 Δ hom2 and Δ fst4 Δ fst4 showed less sesquiterpenes in the HS. However, the sesquiterpenes found in the HS of FRG-deletion strains, namely, ( E )-nerolidol, δ-cadinene, L-calamenene, α-bisabolol and β-bisabolene, were not present in hom2 con or wild-type strains that mainly formed fruiting bodies and barely mycelium. Several sesquiterpenes, including α-guaiene, chamigrene and γ-gurjunene, were only found in presence of fruiting bodies. Our results show remarkable connections between FRGs, fruiting body development and VOC production in S. commune , especially counting for sesquiterpenes. Future studies are needed to reveal whether FRGs directly regulates VOC formation or indirectly by changing the phenotype.

The α-(1,3)-glucan synthase gene agsE impacts the secretome of Aspergillus niger - Jun Lyu; Costanza Torchia; Harm Post; Juan P. Moran Torres; A. F. Maarten Altelaar; Hans de Cock; Han A. B. Wösten (Antonie van Leeuwenhoek, 2023)
Aspergillus niger is widely used as a cell factory for the industrial production of enzymes. Previously, it was shown that deletion of α-1–3 glucan synthase genes results in smaller micro-colonies in liquid cultures of Aspergillus nidulans . Also, it has been shown that small wild-type Aspergillus niger micro-colonies secrete more protein than large mirco-colonies. We here assessed whether deletion of the agsC or agsE α-1–3 glucan synthase genes results in smaller A. niger micro-colonies and whether this is accompanied by a change in protein secretion. Biomass formation was not affected in the deletion strains but pH of the culture medium had changed from 5.2 in the case of the wild-type to 4.6 and 6.4 for Δ agsC and Δ agsE, respectively. The diameter of the Δ agsC micro-colonies was not affected in liquid cultures. In contrast, diameter of the Δ agsE micro-colonies was reduced from 3304 ± 338 µm to 1229 ± 113 µm. Moreover, the Δ agsE secretome was affected with 54 and 36 unique proteins with a predicted signal peptide in the culture medium of MA234.1 and the Δ agsE, respectively. Results show that these strains have complementary cellulase activity and thus may have complementary activity on plant biomass degradation. Together, α-1–3 glucan synthesis (in)directly impacts protein secretion in A. niger .

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Effect of extreme temperatures on asthma hospital visits: Modification by event characteristics and healthy behaviors - Shizhou Deng; Azhu Han; Shuyan Jin; Shuang Wang; Jing Zheng; Bin B. Jalaludin; Shakoor Hajat; Wannian Liang; Cunrui Huang (Environmental Research, 2023)

BasinMaker 3.0: A GIS toolbox for distributed watershed delineation of complex lake-river routing networks - Ming Han; Hongren Shen; Bryan A. Tolson; James R. Craig; Juliane Mai; Simon G.M. Lin; Nandita B. Basu; Frezer S. Awol (Environmental Modelling & Software, 2023)

From remotely‐sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part II—Harnessing data - Ying Sun; Jiaming Wen; Lianhong Gu; Joanna Joiner; Christine Y. Chang; Christiaan van der Tol; Albert Porcar‐Castell; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Although our observing capabilities of solar‐induced chlorophyll fluorescence (SIF) have been growing rapidly, the quality and consistency of SIF datasets are still in an active stage of research and development. As a result, there are considerable inconsistencies among diverse SIF datasets at all scales and the widespread applications of them have led to contradictory findings. The present review is the second of the two companion reviews, and data oriented. It aims to (1) synthesize the variety, scale, and uncertainty of existing SIF datasets, (2) synthesize the diverse applications in the sector of ecology, agriculture, hydrology, climate, and socioeconomics, and (3) clarify how such data inconsistency superimposed with the theoretical complexities laid out in (Sun et al., 2023) may impact process interpretation of various applications and contribute to inconsistent findings. We emphasize that accurate interpretation of the functional relationships between SIF and other ecological indicators is contingent upon complete understanding of SIF data quality and uncertainty. Biases and uncertainties in SIF observations can significantly confound interpretation of their relationships and how such relationships respond to environmental variations. Built upon our syntheses, we summarize existing gaps and uncertainties in current SIF observations. Further, we offer our perspectives on innovations needed to help improve informing ecosystem structure, function, and service under climate change, including enhancing in‐situ SIF observing capability especially in “data desert” regions, improving cross‐instrument data standardization and network coordination, and advancing applications by fully harnessing theory and data.

From remotely sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part I—Harnessing theory - Ying Sun; Lianhong Gu; Jiaming Wen; Christiaan van der Tol; Albert Porcar‐Castell; Joanna Joiner; Christine Y. Chang; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Solar‐induced chlorophyll fluorescence (SIF) is a remotely sensed optical signal emitted during the light reactions of photosynthesis. The past two decades have witnessed an explosion in availability of SIF data at increasingly higher spatial and temporal resolutions, sparking applications in diverse research sectors (e.g., ecology, agriculture, hydrology, climate, and socioeconomics). These applications must deal with complexities caused by tremendous variations in scale and the impacts of interacting and superimposing plant physiology and three‐dimensional vegetation structure on the emission and scattering of SIF. At present, these complexities have not been overcome. To advance future research, the two companion reviews aim to (1) develop an analytical framework for inferring terrestrial vegetation structures and function that are tied to SIF emission, (2) synthesize progress and identify challenges in SIF research via the lens of multi‐sector applications, and (3) map out actionable solutions to tackle these challenges and offer our vision for research priorities over the next 5–10 years based on the proposed analytical framework. This paper is the first of the two companion reviews, and theory oriented. It introduces a theoretically rigorous yet practically applicable analytical framework. Guided by this framework, we offer theoretical perspectives on three overarching questions: (1) The forward (mechanism) question —How are the dynamics of SIF affected by terrestrial ecosystem structure and function? (2) The inference question : What aspects of terrestrial ecosystem structure, function, and service can be reliably inferred from remotely sensed SIF and how? (3) The innovation question : What innovations are needed to realize the full potential of SIF remote sensing for real‐world applications under climate change? The analytical framework elucidates that process complexity must be appreciated in inferring ecosystem structure and function from the observed SIF; this framework can serve as a diagnosis and inference tool for versatile applications across diverse spatial and temporal scales.

The Anthropocene as an epoch is distinct from all other concepts known by this term: a reply to Swindles et al. (2023) - Martin J. Head; Colin N. Waters; Jan A. Zalasiewicz; Anthony D. Barnosky; Simon D. Turner; Alejandro Cearreta; Reinhold Leinfelder; Francine M.G. McCarthy; Daniel de B. Richter; Neil L. Rose; Yoshiki Saito; Davor Vidas; et al. (Journal of Quaternary Science, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Transfer learning in a biomaterial fibrosis model identifies in vivo senescence heterogeneity and contributions to vascularization and matrix production across species and diverse pathologies - Christopher Cherry; James I. Andorko; Kavita Krishnan; Joscelyn C. Mejías; Helen Hieu Nguyen; Katlin B. Stivers; Elise F. Gray-Gaillard; Anna Ruta; Jin Han; Naomi Hamada; Masakazu Hamada; Ines Sturmlechner; et al. (GeroScience, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

The effects of coastal local circulations and their interactions on ozone pollution in the Hangzhou metropolitan area - Z.S. Han; H.N. Liu; B. Yu; X.Y. Wang (Urban Climate, 2023)

Benzimidazole fungicide biotransformation by comammox Nitrospira bacteria: Transformation pathways and associated proteomic responses - Ping Han; Ana B. Rios-Miguel; Xiufeng Tang; Yaochun Yu; Li-Jun Zhou; Lijun Hou; Min Liu; Dongyao Sun; Mike S.M. Jetten; Cornelia U. Welte; Yujie Men; Sebastian Lücker (Journal of Hazardous Materials, 2023)

Response to Merritts et al. (2023): The Anthropocene is complex. Defining it is not - Colin N. Waters; Martin J. Head; Jan Zalasiewicz; Francine M.G. McCarthy; Scott L. Wing; Peter K. Haff; Mark Williams; Anthony D. Barnosky; Barbara Fiałkiewicz-Kozieł; Reinhold Leinfelder; J.R. McNeill; Neil L. Rose; et al. (Earth-Science Reviews, 2023)

Correction: Cryopreservation of Whole Rat Livers by Vitrification and Nanowarming - Anirudh Sharma; Charles Y. Lee; Bat-Erdene Namsrai; Zonghu Han; Diane Tobolt; Joseph Sushil Rao; Zhe Gao; Michael L. Etheridge; Michael Garwood; Mark G. Clemens; John C. Bischof; Erik B. Finger (Annals of Biomedical Engineering, 2023)

Cryopreservation of Whole Rat Livers by Vitrification and Nanowarming - Anirudh Sharma; Charles Y. Lee; Bat-Erdene Namsrai; Zonghu Han; Diane Tobolt; Joseph Sushil Rao; Zhe Gao; Michael L. Etheridge; Michael Garwood; Mark G. Clemens; John C. Bischof; Erik B. Finger (Annals of Biomedical Engineering, 2023)

Bioaccumulation and emission of organophosphate esters in plants affecting the atmosphere's phosphorus cycle - Shengxing Long; Paul B. Hamilton; Bo Fu; Jing Xu; Luchao Han; Xinhao Suo; Yuqin Lai; Guofeng Shen; Fuliu Xu; Bengang Li (Environmental Pollution, 2023)

Correction to: Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2023)

Elastoplastic Modelling of Porous Limestones with Porosity Dependency - B. Han; Q. M. Gong; X. L. Du; Y. Gao; W. Q. Shen; S. Lin (Rock Mechanics and Rock Engineering, 2022)

Differential bone metabolism and protein expression in mice fed a high-fat diet versus Daurian ground squirrels following natural pre-hibernation fattening - Xuli Gao; Shenyang Shen; Qiaohua Niu; Weilan Miao; Yuting Han; Ziwei Hao; Ning An; Yingyu Yang; Yu Zhang; Han Zhang; Kenneth B. Storey; Hui Chang (Journal of Zhejiang University-SCIENCE B, 2022)

Correlation notice on the electrochemical dealloying and antibacterial properties of gold–silver alloy nanoparticles - Javad B. M. Parambath; Islam M. Ahmady; Seema Panicker; Aebin Sin; Changseok Han; Ahmed A. Mohamed (BioMetals, 2022)

Antimicrobial activity of quaternary ammonium salts: structure-activity relationship - Mallikarjuna N. Nadagouda; Pooja Vijayasarathy; Aebin Sin; Heeyeon Nam; Sanaullah Khan; Javad B. M. Parambath; Ahmed A. Mohamed; Changseok Han (Medicinal Chemistry Research, 2022)

The proposed Anthropocene Epoch/Series is underpinned by an extensive array of mid‐20 th century stratigraphic event signals - Martin J. Head; Jan A. Zalasiewicz; Colin N. Waters; Simon D. Turner; Mark Williams; Anthony D. Barnosky; Will Steffen; Michael Wagreich; Peter K. Haff; Jaia Syvitski; Reinhold Leinfelder; Francine M. G. Mccarthy; et al. (Journal of Quaternary Science, 2022)
The extensive array of mid‐20 th century stratigraphic event signals associated with the ‘Great Acceleration’ enables precise and unambiguous recognition of the Anthropocene as an epoch/series within the Geological Time Scale. A mid‐20 th century inception is consistent with Earth System science analysis in which the Anthropocene term and concept arose, and would reflect the reality that our planet has sharply exited the range of natural variability characterizing the Holocene Epoch/Series, which the Anthropocene would therefore terminate. An alternative, recently proposed ‘geological event’ approach to the Anthropocene is primarily an interdisciplinary concept, encompassing historical and socio‐cultural processes and their global environmental impacts over a diachronous timeframe that extends back at least many millennia. Resembling more closely a geological episode than an event , it would decouple the Anthropocene from its chronostratigraphic delineation and association with an abrupt planetary perturbation; but separately defined and differently named it might be usefully complementary. We recommend a clear separation of epochs , events and episodes . An epoch is a formal subdivision of the Geological Time Scale, and its correlation may be assisted by one or more events ; an event is usually, and particularly in the Quaternary, a brief incident or perturbation with a sedimentary expression; and an episode is a longer, internally complex time interval that may include several events and even extend across several epochs.

Inter- and intra-species heterogeneity in germination of Aspergillus conidia - Maryam Ijadpanahsaravi; Wieke R. Teertstra; Han A. B. Wösten (Antonie van Leeuwenhoek, 2022)
Aspergilli are among the most abundant fungi worldwide. They degrade organic material and can be pathogens of plants and animals. Aspergilli spread by forming high numbers of conidia. Germination of these stress resistant asexual spores is characterized by a swelling and a germ tube stage. Here, we show that conidia of Aspergillus niger, Aspergillus oryzae, Aspergillus clavatus , Aspergillus nidulans and Aspergillus terreus show different swelling and germ tube formation dynamics in pure water or in water supplemented with (in)organic nutrients. Apart from inter-species heterogeneity, intra-species heterogeneity was observed within spore populations of the aspergilli except for A. terreus . Sub-populations of conidia differing in size and/or contrast showed different swelling and germ tube formation dynamics. Together, data imply that aspergilli differ in their competitive potential depending on the substrate. Moreover, results suggest that intra-species heterogeneity provides a bet hedging mechanism to optimize survival of aspergilli.

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2022)

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

A hypotonic gel-forming eye drop provides enhanced intraocular delivery of a kinase inhibitor with melanin-binding properties for sustained protection of retinal ganglion cells - Yoo Chun Kim; Henry T. Hsueh; Matthew D. Shin; Cynthia A. Berlinicke; Hyounkoo Han; Nicole M. Anders; Avelina Hemingway; Kirby T. Leo; Renee Ti Chou; HyeYoung Kwon; Matthew B. Appell; Usha Rai; et al. (Drug Delivery and Translational Research, 2022)

Current management of melanoma patients with nodal metastases - Dale Han; Alexander C. J. van Akkooi; Richard J. Straker; Adrienne B. Shannon; Giorgos C. Karakousis; Lin Wang; Kevin B. Kim; Douglas Reintgen (Clinical & Experimental Metastasis, 2022)

Penicillium roqueforti conidia induced by L-amino acids can germinate without detectable swelling - Maarten Punt; Wieke R. Teertstra; Han A. B. Wösten (Antonie van Leeuwenhoek, 2022)

Green Chemistry Production of Codlemone, the Sex Pheromone of the Codling Moth (Cydia pomonella), by Metabolic Engineering of the Oilseed Crop Camelina (Camelina sativa) - Yi-Han Xia; Hong-Lei Wang; Bao-Jian Ding; Glenn P. Svensson; Carin Jarl-Sunesson; Edgar B. Cahoon; Per Hofvander; Christer Löfstedt (Journal of Chemical Ecology, 2021)
Synthetic pheromones have been used for pest control over several decades. The conventional synthesis of di-unsaturated pheromone compounds is usually complex and costly. Camelina ( Camelina sativa ) has emerged as an ideal, non-food biotech oilseed platform for production of oils with modified fatty acid compositions. We used Camelina as a plant factory to produce mono- and di-unsaturated C 12 chain length moth sex pheromone precursors, ( E )-9-dodecenoic acid and ( E , E )-8,10-dodecadienoic acid, by introducing a fatty acyl-ACP thioesterase FatB gene UcTE from California bay laurel ( Umbellularia californica ) and a bifunctional ∆9 desaturase gene Cpo_CPRQ from the codling moth, Cydia pomonella . Different transgene combinations were investigated for increasing pheromone precursor yield. The most productive Camelina line was engineered with a vector that contained one copy of UcTE and the viral suppressor protein encoding P19 transgenes and three copies of Cpo_CPRQ transgene. The T 2 generation of this line produced 9.4% of ( E )-9-dodecenoic acid and 5.5% of ( E , E )-8,10-dodecadienoic acid of the total fatty acids, and seeds were selected to advance top-performing lines to homozygosity. In the T 4 generation, production levels of ( E )-9-dodecenoic acid and ( E , E )-8,10-dodecadienoic acid remained stable. The diene acid together with other seed fatty acids were converted into corresponding alcohols, and the bioactivity of the plant-derived codlemone was confirmed by GC-EAD and a flight tunnel assay. Trapping in orchards and home gardens confirmed significant and specific attraction of C. pomonella males to the plant-derived codlemone.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

The second wave of earthworm invasions in North America: biology, environmental impacts, management and control of invasive jumping worms - Chih-Han Chang; Marie L. C. Bartz; George Brown; Mac A. Callaham; Erin K. Cameron; Andrea Dávalos; Annise Dobson; Josef H. Görres; Bradley M. Herrick; Hiroshi Ikeda; Samuel W. James; Marie R. Johnston; et al. (Biological Invasions, 2021)

Social disruption–induced stress pre-exposure aggravates, while the presence of conspecifics diminishes, acetic acid–induced writhing - Yi-Han Liao; Yi-Chi Su; Yu-Han Huang; Hao Chen; Ya-Hsuan Chan; Li-Han Sun; Chianfang G. Cherng; Ing-Tiau B. Kuo; Lung Yu (Psychopharmacology, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

Use of Moringa oleifera seeds powder as bio-coagulants for the surface water treatment - H. T. Nhut; N. T. Q. Hung; B. Q. Lap; L. T. N. Han; T. Q. Tri; N. H. K. Bang; N. T. Hiep; N. M. Ky (International Journal of Environmental Science and Technology, 2021)

Maize Endochitinase Expression in Response to Fall Armyworm Herbivory - Yang Han; Erin B. Taylor; Dawn Luthe (Journal of Chemical Ecology, 2021)

Impact of tibetan plateau snow cover on tropical cyclogenesis via the Madden–Julian oscillation during the following boreal summer - Xiang Han; Haikun Zhao; Philip J. Klotzbach; Liguang Wu; Graciela B. Raga (Climate Dynamics, 2021)

ValSten: a new wild species derived allotetraploid for increasing genetic diversity of the peanut crop (Arachis hypogaea L.) - Dongying Gao; Ana C. G. Araujo; Eliza F. M. B. Nascimento; M. Carolina Chavarro; Han Xia; Scott A. Jackson; David J. Bertioli; Soraya C. M. Leal-Bertioli (Genetic Resources and Crop Evolution, 2021)
Introgression of desirable traits from wild relatives plays an important role in crop improvement, as wild species have important characters such as high resistance to pests and pathogens. However, use of wild peanut relatives is challenging because almost all wild species are diploid and sexually incompatible with cultivated peanut, which is tetraploid (AABB genome type; 2 n = 4x = 40). To overcome the ploidy barrier, we used 2 wild species to make a tetraploid with the same allotetraploid genome composition as cultivated peanut. Crosses were made between 2 diploid wild species, Arachis valida Krapov. and W.C. Greg. (BB genome; 2 n = 2x = 20) and Arachis stenosperma Krapov. and W.C. Greg. (AA genome; 2 n = 2x = 20). Cuttings from the diploid F 1 AB hybrid were treated with colchicine to induce chromosome doubling thus generating an induced allotetraploid. Chromosome counts confirmed polyploidy (AABB genome; 2 n = 4x = 40). We named the new allotetraploid ValSten. Plants had well-developed fertile pollen, produced abundant seed and were sexually compatible with cultivated peanut. ValSten exhibits the same high resistance to early and late leaf spot and rust as its diploid parents. Notably, we observed morphological variations, including flower width and branch angles in the earliest generation (S 0 ) of allotetraploids. A SNP array was used to genotype 47 S 0 allotetraploids. The great majority of markers showed the additive allelic state from both parents (AABB). However, some loci were AAAA or BBBB, indicating homeologous recombination. ValSten provides a new, vigorous, highly fertile, disease resistant germplasm for peanut research and improvement.

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

Gga-miR-181a modulates ANP32A expression and inhibits MDCC-MSB-1 cell - X. Li; C. Zhao; B. Han; L. Qu; C. Liu; N. Yang; L. Lian (In Vitro Cellular & Developmental Biology - Animal, 2021)

Cycling in degradation of organic polymers and uptake of nutrients by a litter‐degrading fungus - Aurin M. Vos; Robert‐Jan Bleichrodt; Koen C. Herman; Robin A. Ohm; Karin Scholtmeijer; Heike Schmitt; Luis G. Lugones; Han A. B. Wösten (Environmental Microbiology, 2021)
Summary Wood and litter degrading fungi are the main decomposers of lignocellulose and thus play a key role in carbon cycling in nature. Here, we provide evidence for a novel lignocellulose degradation strategy employed by the litter degrading fungus Agaricus bisporus (known as the white button mushroom). Fusion of hyphae allows this fungus to synchronize the activity of its mycelium over large distances (50 cm). The synchronized activity has a 13‐h interval that increases to 20 h before becoming irregular and it is associated with a 3.5‐fold increase in respiration, while compost temperature increases up to 2°C. Transcriptomic analysis of this burst‐like phenomenon supports a cyclic degradation of lignin, deconstruction of (hemi‐) cellulose and microbial cell wall polymers, and uptake of degradation products during vegetative growth of A. bisporus . Cycling in expression of the ligninolytic system, of enzymes involved in saccharification, and of proteins involved in nutrient uptake is proposed to provide an efficient way for degradation of substrates such as litter.

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Improving the Diagnostic Ability of the Sleep Apnea Screening System Based on Oximetry by Using Physical Activity Data - Cheng-Han Wu; Jui-Hsuan Lee; Terry B. J. Kuo; Chun-Ting Lai; Lieber P. H. Li; Cheryl C. H. Yang (Journal of Medical and Biological Engineering, 2020)

Apical but not sub-apical hyphal compartments are self-sustaining in growth - Martin Tegelaar; George P. A. van der Lans; Han A. B. Wösten (Antonie van Leeuwenhoek, 2020)
It was recently demonstrated that apical compartments of Aspergillus niger hyphae are self-sustaining in growth. This was shown by assessing the growth rate of individual hyphae before and after dissection of the second compartment. Using the same methodology, it is here demonstrated that single apical compartments of the septate fungi Penicillium chrysogenum and Schizophyllum commune as well as the 500-µm-apical region of the non-septate fungus Rhizopus stolonifer are also self-sustaining in growth. In contrast, single 2nd compartments (obtained by dissection of the first and third compartment) of the septate fungi or the region between 500 and 1000 µm from tips of R. stolonifer were severely impacted in their growth rate. In addition, it is shown that existing or newly formed branches originating from the 2nd compartments function as a backup system for hyphal growth when the apical part of the hypha of the three studied fungi is damaged. Together, it is concluded that the apical compartments/zones of the studied fungi are self-sustaining in growth. In contrast, the subapical region is not self-sustaining but functions as a backup once the apical zone is damaged. This back up system is relevant in nature because the apices of hyphae are the first to be exposed to (a)biotic stress conditions when entering an unexplored substrate.

Variation and evolution of C:N ratio among different organs enable plants to adapt to N‐limited environments - Jiahui Zhang; Nianpeng He; Congcong Liu; Li Xu; Zhi Chen; Ying Li; Ruomeng Wang; Guirui Yu; Wei Sun; Chunwang Xiao; Han Y. H. Chen; Peter B. Reich (Global Change Biology, 2020)
Carbon (C) and nitrogen (N) are the primary elements involved in the growth and development of plants. The C:N ratio is an indicator of nitrogen use efficiency (NUE) and an input parameter for some ecological and ecosystem models. However, knowledge remains limited about the convergent or divergent variation in the C:N ratios among different plant organs (e.g., leaf, branch, trunk, and root) and how evolution and environment affect the coefficient shifts. Using systematic measurements of the leaf–branch–trunk–root of 2,139 species from tropical to cold‐temperate forests, we comprehensively evaluated variation in C:N ratio in different organs in different taxa and forest types. The ratios showed convergence in the direction of change but divergence in the rate of change. Plants evolved toward lower C:N ratios in the leaf and branch, with N playing a more important role than C. The C:N ratio of plant organs (except for the leaf) was constrained by phylogeny, but not strongly. Both the change of C:N during evolution and its spatial variation (lower C:N ratio at midlatitudes) help develop the adaptive growth hypothesis. That is, plants with a higher C:N ratio promote NUE under strong N‐limited conditions to ensure survival priority, whereas plants with a lower C:N ratio under less N‐limited environments benefit growth priority. In nature, larger proportion of species with a high C:N ratio enabled communities to inhabit more N‐limited conditions. Our results provide new insights on the evolution and drivers of C:N ratio among different plant organs, as well as provide a quantitative basis to optimize land surface process models.

Acclimation of leaf respiration consistent with optimal photosynthetic capacity - Han Wang; Owen K. Atkin; Trevor F. Keenan; Nicholas G. Smith; Ian J. Wright; Keith J. Bloomfield; Jens Kattge; Peter B. Reich; I. Colin Prentice (Global Change Biology, 2020)
Plant respiration is an important contributor to the proposed positive global carbon‐cycle feedback to climate change. However, as a major component, leaf mitochondrial (‘dark’) respiration ( R d ) differs among species adapted to contrasting environments and is known to acclimate to sustained changes in temperature. No accepted theory explains these phenomena or predicts its magnitude. Here we propose that the acclimation of R d follows an optimal behaviour related to the need to maintain long‐term average photosynthetic capacity ( V cmax ) so that available environmental resources can be most efficiently used for photosynthesis. To test this hypothesis, we extend photosynthetic co‐ordination theory to predict the acclimation of R d to growth temperature via a link to V cmax , and compare predictions to a global set of measurements from 112 sites spanning all terrestrial biomes. This extended co‐ordination theory predicts that field‐measured R d and V cmax accessed at growth temperature ( R d,tg and V cmax,tg ) should increase by 3.7% and 5.5% per degree increase in growth temperature. These acclimated responses to growth temperature are less steep than the corresponding instantaneous responses, which increase 8.1% and 9.9% per degree of measurement temperature for R d and V cmax respectively. Data‐fitted responses proof indistinguishable from the values predicted by our theory, and smaller than the instantaneous responses. Theory and data are also shown to agree that the basal rates of both R d and V cmax assessed at 25°C ( R d,25 and V cmax,25 ) decline by ~4.4% per degree increase in growth temperature. These results provide a parsimonious general theory for R d acclimation to temperature that is simpler—and potentially more reliable—than the plant functional type‐based leaf respiration schemes currently employed in most ecosystem and land‐surface models.

Rare species, functional groups, and evolutionary lineages drive successional trajectories in disturbed forests - Simon Thorn; Anne Chao; Markus Bernhardt‐Römermann; Yan‐Han Chen; Kostadin B. Georgiev; Christoph Heibl; Jörg Müller; Hanno Schäfer; Claus Bässler (Ecology, 2020)
Following natural disturbances, additional anthropogenic disturbance may alter community recovery by affecting the occurrences of species, functional groups, and evolutionary lineages. However, our understanding of whether rare, common, or dominant species, functional groups, or evolutionary lineages are most strongly affected by an additional disturbance, particularly across multiple taxa, is limited. Here, we used a generalized diversity concept based on Hill numbers to quantify the community differences of vascular plants, bryophytes, lichens, wood‐inhabiting fungi, saproxylic beetles, and birds in a storm‐disturbed, experimentally salvage logged forest. Communities of all investigated species groups showed dissimilarities between logged and unlogged plots. Most species groups showed no significant changes in dissimilarities between logged and unlogged plots over the first seven years of succession, indicating a lack of community recovery. In general, the dissimilarities of communities were mainly driven by rare species. Convergence of dissimilarities occurred more often than divergence during the early stages of succession for rare species, indicating a major role in driving decreasing taxonomic dissimilarities between logged and unlogged plots over time. Trends in species dissimilarities only partially match the trends in dissimilarities of functional groups and evolutionary lineages, with little significant changes in successional trajectories. Nevertheless, common and dominant species contributed to a convergence of dissimilarities over time in the case of the functional dissimilarities of wood‐inhabiting fungi. Our study shows that salvage logging following disturbances can alter successional trajectories in early stages of forest succession following natural disturbances. However, community changes over time may differ remarkably in different taxonomic groups and are best detected based on taxonomic, rather than functional or phylogenetic dissimilarities.

Role of Adult Tissue-Derived Pluripotent Stem Cells in Bone Regeneration - Liudmila Leppik; K. Sielatycka; D. Henrich; Z. Han; H. Wang; M. J. Eischen-Loges; K. M. C. Oliveira; M. B. Bhavsar; M. Z. Ratajczak; J. H. Barker (Stem Cell Reviews and Reports, 2020)
Background Bone marrow-derived mononuclear cells (BM-MNC) consist of a heterogeneous mix of mesenchymal stem cells (MSC), hematopoietic progenitor cells (HPC), endothelial progenitor cells (EPC), monocytes, lymphocytes and pluripotent stem cells. Whereas the importance of MSC and EPC has been well documented in bone healing and regeneration studies, the role of pluripotent stem cells is still poorly understood. In the present study we evaluated if and how Very Small Embryonic Like cells (VSEL), isolated from rat BM-MNC, contribute to bone healing. Methods Large bone defects were made in the femurs of 38 Sprague Dawley female rats and treated with β-TCP scaffold granules seeded with male VSEL; BM-MNC, VSEL-depleted BM-MNC or scaffold alone, and bone healing was evaluated at 8 weeks post-surgery. Results Bone healing was significantly increased in defects treated with VSEL and BM-MNC, compared to defects treated with VSEL-depleted BM-MNC. Donor cells were detected in new bone tissue, in all the defects treated with cells, and in fibrous tissue only in defects treated with VSEL-depleted BM-MNC. The number of CD68+ cells was the highest in the VSEL-depleted group, whereas the number of TRAP positive cells was the lowest in this group. Conclusions Based on the results, we can conclude that VSEL play a role in BM-MNC induced bone formation. In our rat femur defect model, in defects treated with VSEL-depleted BM-MNC, osteoclastogenesis and bone formation were decreased, and foreign body reaction was increased.

Modulation of boreal extended summer tropical cyclogenesis over the northwest Pacific by the quasi‐biweekly oscillation under different El Niño‐southern oscillation phases - Xiang Han; Haikun Zhao; Xun Li; Graciela B. Raga; Chao Wang; Qingqing Li (International Journal of Climatology, 2020)
The study of the interannual and intraseasonal modulation of tropical cyclogenesis (TCG) in the northwest Pacific (NWP) basin has received significant attention in the past. Most previous studies have focused on the individual impact of El Niño‐southern oscillation (ENSO) or Madden–Julian Oscillation on TCG, whereas the combined effect of ENSO and another leading intraseasonal oscillation mode, quasi‐biweekly oscillation (QBWO), on NWP TCG has rarely been studied. Therefore, this study systemically investigates the modulation of NWP TCG by the QBWO under different ENSO phases. A significant modulation of TCG by QBWO in the ENSO neutral years is observed, with significantly increased (decreased) TCG over the NWP in QBWO active (inactive) phases. Moreover, during El Niño years and La Niña years, the modulation of TCG by QBWO is not significant and no distinctive difference in the TCG frequency can be detected. Further analyses show that the modulation of TCG by the QBWO is mainly related to the changes in large‐scale environment and energy that affect TCG associated with active or inactive phases of the QBWO under different ENSO phases. Large‐scale environmental factors and energy are more favourable for TCG during ENSO neutral years compared with El Niño and La Niña years. These results are associated with QBWO cycle under the impact of background (e.g., boundary layer moisture and zonal wind shear) which is determined by ENSO conditions.

Exploiting the reference genome sequence of hexaploid wheat: a proteomic study of flour proteins from the cultivar Chinese Spring - Susan B. Altenbach; Han-Chang Chang; Annamaria Simon-Buss; Toni Mohr; Naxin Huo; Yong Q. Gu (Functional & Integrative Genomics, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Subpopulations of hyphae secrete proteins or resist heat stress in Aspergillus oryzae colonies - Martin Tegelaar; Robert‐Jan Bleichrodt; Benjamin Nitsche; Arthur F. J. Ram; Han A. B. Wösten (Environmental Microbiology, 2020)
Summary Hyphae at the outer part of colonies of Aspergillus niger and Aspergillus oryzae are heterogeneous with respect to transcriptional and translational activity. This heterogeneity is maintained by Woronin body mediated closure of septal pores that block interhyphal mixing of cytoplasm. Indeed, heterogeneity between hyphae is abolished in Δ hexA strains that lack Woronin bodies. The subpopulation of hyphae with high transcriptional and translational activity secretes enzymes that degrade the substrate resulting in breakdown products that serve as nutrients. The role of hyphae with low transcriptional and translational activity was not yet known. Here, we show that this subpopulation is more resistant to environmental stress in A . oryzae , in particular to temperature stress, when compared to hyphae with high transcriptional and translational activity. Notably, all hyphae of the Δ hexA strain of A . oryzae were sensitive to heat stress explained by the reduced heterogeneity in this strain. Together, we show that different subpopulations of hypha secrete proteins and resist heat stress showing the complexity of a fungal mycelium.

Complementarity effects are strengthened by competition intensity and global environmental change in the central boreal forests of Canada - Eric B. Searle; Han Y. H. Chen (Ecology Letters, 2020)
Increases in niche complementarity have been hypothesised to reduce the intensity of interspecific competition within natural forests. In regions currently experiencing potentially enhanced growth under global environmental change, niche complementarity may become even more beneficial. However, few studies have provided direct evidence of this mechanism. Here, we use data from 180 permanent sample plots in Manitoba, Canada, with a full spatial mapping of all stems, to show that complementarity effects on average increased with neighbourhood competition intensity and temporally rising CO 2 , warming and water availability. Importantly, complementarity effects increased with both shade tolerance and phylogenetic dissimilarity between the focal tree and its neighbours. Our results provide further evidence that increasing stand functional and phylogenetic diversity can improve individual tree productivity, especially for individuals experiencing intense competition and may offer an avenue to maintain productivity under global environmental change.

Consensus Paper: Experimental Neurostimulation of the Cerebellum - Lauren N. Miterko; Kenneth B. Baker; Jaclyn Beckinghausen; Lynley V. Bradnam; Michelle Y. Cheng; Jessica Cooperrider; Mahlon R. DeLong; Simona V. Gornati; Mark Hallett; Detlef H. Heck; Freek E. Hoebeek; Abbas Z. Kouzani; et al. (The Cerebellum, 2019)

Difference in survival between right- versus left-sided colorectal neuroendocrine neoplasms - Ge-han Xu; Hua-wei Zou; Ashley B. Grossman (Journal of Zhejiang University-SCIENCE B, 2019)

Plant and microalgae consortium for an enhanced biodegradation of sulfamethazine - Jiu-Qiang Xiong; Byong-Hun Jeon; Sanjay P. Govindwar; Mayur B. Kurade; Swapnil M. Patil; Jung-Han Park; Ki-Hyun Kim (Environmental Science and Pollution Research, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

A Sustained Ocean Observing System in the Indian Ocean for Climate Related Scientific Knowledge and Societal Needs - J. C. Hermes; Y. Masumoto; L. M. Beal; M. K. Roxy; J. Vialard; M. Andres; H. Annamalai; S. Behera; N. D’Adamo; T. Doi; M. Feng; W. Han; et al. (Frontiers in Marine Science, 2019)

Operating characteristics of stepwise covariate selection in pharmacometric modeling - Malidi Ahamadi; Anna Largajolli; Paul M. Diderichsen; Rik de Greef; Thomas Kerbusch; Han Witjes; Akshita Chawla; Casey B. Davis; Ferdous Gheyas (Journal of Pharmacokinetics and Pharmacodynamics, 2019)

Species‐rich boreal forests grew more and suffered less mortality than species‐poor forests under the environmental change of the past half‐century - Masumi Hisano; Han Y. H. Chen; Eric B. Searle; Peter B. Reich (Ecology Letters, 2019)
Climate and other global environmental changes are major threats to ecosystem functioning and biodiversity. However, the importance of plant diversity in mitigating the responses of functioning of natural ecosystems to long‐term environmental change remains unclear. Using inventory data of boreal forests of western Canada from 1958 to 2011, we found that aboveground biomass growth increased over time in species‐rich forests but decreased in species‐poor forests, and importantly, aboveground biomass loss from tree mortality was smaller in species‐rich than species‐poor forests. A further analysis indicated that growth of species‐rich (but not species‐poor) forests was statistically positively associated with rising CO 2 , and that mortality in species‐poor forests increased more as climate moisture availability decreased than it did in species‐rich forests. In contrast, growth decreased and mortality increased as the climate warmed regardless of species diversity. Our results suggest that promoting high tree diversity may help reduce the climate and environmental change vulnerability of boreal forests.

Correction to: Monitoring Dose Response of Cyanide Antidote Dimethyl Trisulfide in Rabbits Using Diffuse Optical Spectroscopy - Jangwoen Lee; Gary Rockwood; Brian Logue; Erica Manandhar; Ilona Petrikovics; Changhoon Han; Vikhyat Bebarta; Sari B. Mahon; Tanya Burney; Matthew Brenner (Journal of Medical Toxicology, 2019)

Monitoring Dose Response of Cyanide Antidote Dimethyl Trisulfide in Rabbits Using Diffuse Optical Spectroscopy - Jangwoen Lee; Gary Rockwood; Brian Logue; Erica Manandhar; Ilona Petrikovics; Changhoon Han; Vik Bebarta; Sari B. Mahon; Tanya Burney; Matthew Brenner (Journal of Medical Toxicology, 2018)

Detecting hydrological consistency between soil moisture and precipitation and changes of soil moisture in summer over the Tibetan Plateau - X. Meng; R. Li; L. Luan; S. Lyu; T. Zhang; Y. Ao; B. Han; L. Zhao; Y. Ma (Climate Dynamics, 2018)

A hybrid proline-rich cell-wall protein gene JsPRP1 from Juglans sigillata Dode confers both biotic and abiotic stresses in transgenic tobacco plants - D. Q. Liu; Q. Han; T. Shah; C. Y. Chen; Q. Wang; B. F. Tang; F. Ge (Trees, 2018)

Carbon Storage Declines in Old Boreal Forests Irrespective of Succession Pathway - Bilei Gao; Anthony R. Taylor; Eric B. Searle; Praveen Kumar; Zilong Ma; Alexandra M. Hume; Han Y. H. Chen (Ecosystems, 2018)

Lymph node metastasis in melanoma: a debate on the significance of nodal metastases, conditional survival analysis and clinical trials - Mark B. Faries; Dale Han; Michael Reintgen; Lauren Kerivan; Douglas Reintgen; Corrado Caracò (Clinical & Experimental Metastasis, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Observed and modelled temperature and precipitation extremes over Southeast Asia from 1972 to 2010 - W. K. Cheong; B. Timbal; N. Golding; S. Sirabaha; K. F. Kwan; T. A. Cinco; B. Archevarahuprok; V. H. Vo; D. Gunawan; S. Han (International Journal of Climatology, 2018)
Regional assessments of trends in climate extremes are necessary for countries to make informed decisions about adaptation strategies and to put these changes into a global context. A workshop bringing together several Southeast Asian countries has delivered a new set of daily weather observations suitable to analyse the changes in temperature and precipitation extremes between 1972 and 2010. The use of a consistent and widely tested methodology in this study allows a direct comparison with results from other parts of the world. Trends in a range of climate extremes indices were assessed focusing on spatial variation in these trends. For most locations temperature trends obtained in this study appear broadly consistent with previous assessments; for some locations stronger trends have been detected through the inclusion of new data. In contrast to earlier studies, evidence of trends in precipitation extremes is emerging, with significant increasing trends in both regional and subregional data. In addition, large correlations between regional rainfall extremes and large‐scale features such as El Niño‐Southern Oscillation and the Indian Ocean Dipole were identified. Finally, the observed trends are compared with a regional climate model reconstruction of the historical period. It was found that the model captures very well the trends and spatial variation of temperature extremes across the region, albeit with an underestimation of the more extreme indices. In contrast, the trends in precipitation extremes are largely overestimated, particularly in the western side of Southeast Asia.

The FlbA-regulated predicted transcription factor Fum21 of Aspergillus niger is involved in fumonisin production - David Aerts; Esther E. Hauer; Robin A. Ohm; Mark Arentshorst; Wieke R. Teertstra; Christopher Phippen; Arthur F. J. Ram; Jens C. Frisvad; Han A. B. Wösten (Antonie van Leeuwenhoek, 2018)

Temporal changes in soil C‐N‐P stoichiometry over the past 60 years across subtropical China - Zaipeng Yu; Minhuang Wang; Zhiqun Huang; Teng‐Chiu Lin; Matthew A. Vadeboncoeur; Eric B. Searle; Han Y. H. Chen (Global Change Biology, 2018)
Controlled experiments have shown that global changes decouple the biogeochemical cycles of carbon (C), nitrogen (N), and phosphorus (P), resulting in shifting stoichiometry that lies at the core of ecosystem functioning. However, the response of soil stoichiometry to global changes in natural ecosystems with different soil depths, vegetation types, and climate gradients remains poorly understood. Based on 2,736 observations along soil profiles of 0–150 cm depth from 1955 to 2016, we evaluated the temporal changes in soil C‐N‐P stoichiometry across subtropical China, where soils are P‐impoverished, with diverse vegetation, soil, and parent material types and a wide range of climate gradients. We found a significant overall increase in soil total C concentration and a decrease in soil total P concentration, resulting in increasing soil C:P and N:P ratios during the past 60 years across all soil depths. Although average soil N concentration did not change, soil C:N increased in topsoil while decreasing in deeper soil. The temporal trends in soil C‐N‐P stoichiometry differed among vegetation, soil, parent material types, and spatial climate variations, with significantly increased C:P and N:P ratios for evergreen broadleaf forest and highly weathered Ultisols, and more pronounced temporal changes in soil C:N, N:P, and C:P ratios at low elevations. Our sensitivity analysis suggests that the temporal changes in soil stoichiometry resulted from elevated N deposition, rising atmospheric CO 2 concentration and regional warming. Our findings revealed that the responses of soil C‐N‐P and stoichiometry to long‐term global changes have occurred across the whole soil depth in subtropical China and the magnitudes of the changes in soil stoichiometry are dependent on vegetation types, soil types, and spatial climate variations.

An Experimental Study of Dependence of Optimum TBM Cutter Spacing on Pre-set Penetration Depth in Sandstone Fragmentation - D. Y. Han; P. Cao; J. Liu; J. B. Zhu (Rock Mechanics and Rock Engineering, 2017)

Fungal Denitrification Activity in Vertical Flow Constructed Wetlands as Impacted by Plant Species Richness, Carbon, Nitrogen and pH Amendments - W. L. Liu; C. B. Zhang; W. J. Han; M. Guan; S. Y. Liu; Y. Ge; J. Chang (Bulletin of Environmental Contamination and Toxicology, 2017)

Comparative and population genomic landscape of Phellinus noxius : A hypervariable fungus causing root rot in trees - Chia‐Lin Chung; Tracy J. Lee; Mitsuteru Akiba; Hsin‐Han Lee; Tzu‐Hao Kuo; Dang Liu; Huei‐Mien Ke; Toshiro Yokoi; Marylette B. Roa; Mei‐Yeh J. Lu; Ya‐Yun Chang; Pao‐Jen Ann; et al. (Molecular Ecology, 2017)
The order Hymenochaetales of white rot fungi contain some of the most aggressive wood decayers causing tree deaths around the world. Despite their ecological importance and the impact of diseases they cause, little is known about the evolution and transmission patterns of these pathogens. Here, we sequenced and undertook comparative genomic analyses of Hymenochaetales genomes using brown root rot fungus Phellinus noxius , wood‐decomposing fungus Phellinus lamaensis, laminated root rot fungus Phellinus sulphurascens and trunk pathogen Porodaedalea pini . Many gene families of lignin‐degrading enzymes were identified from these fungi, reflecting their ability as white rot fungi. Comparing against distant fungi highlighted the expansion of 1,3‐beta‐glucan synthases in P. noxius , which may account for its fast‐growing attribute. We identified 13 linkage groups conserved within Agaricomycetes, suggesting the evolution of stable karyotypes. We determined that P. noxius has a bipolar heterothallic mating system, with unusual highly expanded ~60 kb A locus as a result of accumulating gene transposition. We investigated the population genomics of 60 P. noxius isolates across multiple islands of the Asia Pacific region. Whole‐genome sequencing showed this multinucleate species contains abundant poly‐allelic single nucleotide polymorphisms with atypical allele frequencies. Different patterns of intra‐isolate polymorphism reflect mono‐/heterokaryotic states which are both prevalent in nature. We have shown two genetically separated lineages with one spanning across many islands despite the geographical barriers. Both populations possess extraordinary genetic diversity and show contrasting evolutionary scenarios. These results provide a framework to further investigate the genetic basis underlying the fitness and virulence of white rot fungi.

Seasonal modeling of hand, foot, and mouth disease as a function of meteorological variations in Chongqing, China - Pin Wang; Han Zhao; Fangxin You; Hailong Zhou; William B. Goggins (International Journal of Biometeorology, 2017)

Erratum to: Ocean atmosphere thermal decoupling in the eastern equatorial Indian ocean - Sudheer Joseph; M. Ravichandran; B. Praveen Kumar; Raju V. Jampana; Weiqing Han (Climate Dynamics, 2017)

Ocean atmosphere thermal decoupling in the eastern equatorial Indian ocean - Sudheer Joseph; M. Ravichandran; B. Praveen Kumar; Raju V. Jampana; Weiqing Han (Climate Dynamics, 2017)

Genetic structure and population history of wintering Asian Great Bustard (Otis tarda dybowskii) in China: implications for conservation - Gang Liu; Xiaolong Hu; Aaron B. A. Shafer; Minghao Gong; Morigen Han; Changjiang Yu; Jingying Zhou; Jie Bai; Derong Meng; Guohai Yu; Dapeng Dang (Journal of Ornithology, 2017)

Effect of Microneedle Type on Transdermal Permeation of Rizatriptan - Chandrateja Uppuluri; Ashraf Sultana Shaik; Tao Han; Atul Nayak; Karthik J. Nair; Benjamin R. Whiteside; Buchi N. Nalluri; Diganta B. Das (AAPS PharmSciTech, 2017)

IGF-1 has sexually dimorphic, pleiotropic, and time-dependent effects on healthspan, pathology, and lifespan - Nicole M. Ashpole; Sreemathi Logan; Andriy Yabluchanskiy; Matthew C. Mitschelen; Han Yan; Julie A. Farley; Erik L. Hodges; Zoltan Ungvari; Anna Csiszar; Sixia Chen; Constantin Georgescu; Gene B. Hubbard; et al. (GeroScience, 2017)

In vitro cytotoxicity assessment of a West Virginia chemical spill mixture involving 4-methylcyclohexanemethanol and propylene glycol phenyl ether - Alice A. Han; Emily B. Fabyanic; Julie V. Miller; Maren S. Prediger; Nicole Prince; Julia A. Mouch; Jonathan Boyd (Environmental Monitoring and Assessment, 2017)

Ectomycorrhizal fungal response to warming is linked to poor host performance at the boreal‐temperate ecotone - Christopher W. Fernandez; Nhu H. Nguyen; Artur Stefanski; Ying Han; Sarah E. Hobbie; Rebecca A. Montgomery; Peter B. Reich; Peter G. Kennedy (Global Change Biology, 2017)
Rising temperatures associated with climate change have been shown to negatively affect the photosynthetic rates of boreal forest tree saplings at their southern range limits. To quantify the responses of ectomycorrhizal ( EM ) fungal communities associated with poorly performing hosts, we sampled the roots of Betula papyrifera and Abies balsamea saplings growing in the B4Warmed (Boreal Forest Warming at an Ecotone in Danger) experiment. EM fungi on the root systems of both hosts were compared from ambient and +3.4 °C air and soil warmed plots at two sites in northern Minnesota. EM fungal communities were assessed with high‐throughput sequencing along with measures of plant photosynthesis, soil temperature, moisture, and nitrogen. Warming selectively altered EM fungal community composition at both the phylum and genus levels, but had no significant effect on EM fungal operational taxonomic unit ( OTU ) diversity. Notably, warming strongly favored EM Ascomycetes and EM fungi with short‐contact hyphal exploration types. Declining host photosynthetic rates were also significantly inversely correlated with EM Ascomycete and EM short‐contact exploration type abundance, which may reflect a shift to less carbon demanding fungi due to lower photosynthetic capacity. Given the variation in EM host responses to warming, both within and between ecosystems, better understanding the link between host performance and EM fungal community structure will to clarify how climate change effects cascade belowground.

The Next Decade of Big Data in Ecosystem Science - S. L. LaDeau; B. A. Han; E. J. Rosi-Marshall; K. C. Weathers (Ecosystems, 2017)

Anchoring climate change communications - Adam J. L. Harris; Han-Hui Por; Stephen B. Broomell (Climatic Change, 2017)

Persistent and pervasive compositional shifts of western boreal forest plots in Canada - Eric B. Searle; Han Y. H. Chen (Global Change Biology, 2017)
Species compositional shifts have important consequences to biodiversity and ecosystem function and services to humanity. In boreal forests, compositional shifts from late‐successional conifers to early‐successional conifers and deciduous broadleaves have been postulated based on increased fire frequency associated with climate change truncating stand age‐dependent succession. However, little is known about how climate change has affected forest composition in the background between successive catastrophic fires in boreal forests. Using 1797 permanent sample plots from western boreal forests of Canada measured from 1958 to 2013, we show that after accounting for stand age‐dependent succession, the relative abundances of early‐successional deciduous broadleaves and early‐successional conifers have increased at the expense of late‐successional conifers with climate change. These background compositional shifts are persistent temporally, consistent across all forest stand ages and pervasive spatially across the region. Rising atmospheric CO 2 promoted early‐successional conifers and deciduous broadleaves, and warming increased early‐successional conifers at the expense of late‐successional conifers, but compositional shifts were not associated with climate moisture index. Our results emphasize the importance of climate change on background compositional shifts in the boreal forest and suggest further compositional shifts as rising CO 2 and warming will continue in the 21st century.

The effects of petroleum-contaminated soil on photosynthesis of Amorpha fruticosa seedlings - G. Han; B. X. Cui; X. X. Zhang; K. R. Li (International Journal of Environmental Science and Technology, 2016)

Phosphorus accumulates faster than nitrogen globally in freshwater ecosystems under anthropogenic impacts - Zhengbing Yan; Wenxuan Han; Josep Peñuelas; Jordi Sardans; James J. Elser; Enzai Du; Peter B. Reich; Jingyun Fang (Ecology Letters, 2016)
Combined effects of cumulative nutrient inputs and biogeochemical processes that occur in freshwater under anthropogenic eutrophication could lead to myriad shifts in nitrogen (N):phosphorus (P) stoichiometry in global freshwater ecosystems, but this is not yet well‐assessed. Here we evaluated the characteristics of N and P stoichiometries in bodies of freshwater and their herbaceous macrophytes across human‐impact levels, regions and periods. Freshwater and its macrophytes had higher N and P concentrations and lower N : P ratios in heavily than lightly human‐impacted environments, further evidenced by spatiotemporal comparisons across eutrophication gradients. N and P concentrations in freshwater ecosystems were positively correlated and N : P was negatively correlated with population density in China. These results indicate a faster accumulation of P than N in human‐impacted freshwater ecosystems, which could have large effects on the trophic webs and biogeochemical cycles of estuaries and coastal areas by freshwater loadings, and reinforce the importance of rehabilitating these ecosystems.

Experimental Investigation on Mechanical Behavior and Permeability Evolution of a Porous Limestone Under Compression - B. Han; S. Y. Xie; J. F. Shao (Rock Mechanics and Rock Engineering, 2016)

Climate change‐associated trends in net biomass change are age dependent in western boreal forests of Canada - Han Y. H. Chen; Yong Luo; Peter B. Reich; Eric B. Searle; Shekhar R. Biswas (Ecology Letters, 2016)
The impacts of climate change on forest net biomass change are poorly understood but critical for predicting forest's contribution to the global carbon cycle. Recent studies show climate change‐associated net biomass declines in mature forest plots. The representativeness of these plots for regional forests, however, remains uncertain because we lack an assessment of whether climate change impacts differ with forest age. Using data from plots of varying ages from 17 to 210 years, monitored from 1958 to 2011 in western Canada, we found that climate change has little effect on net biomass change in forests ≤ 40 years of age due to increased growth offsetting increased mortality, but has led to large decreases in older forests due to increased mortality accompanying little growth gain. Our analysis highlights the need to incorporate forest age profiles in examining past and projecting future forest responses to climate change.

Phenotypic plasticity controls regional-scale variation in Quercus variabilis leaf δ13C - Xiao Sun; Hongzhang Kang; Han Y. H. Chen; Baoming Du; Shan Yin; Xuan Zhou; Eric B. Searle; Chunjiang Liu (Trees, 2016)

Application of Microneedle Arrays for Enhancement of Transdermal Permeation of Insulin: In Vitro Experiments, Scaling Analyses and Numerical Simulations - V. Leeladurga; U. Chandra Teja; S. K. Ashraf Sultana; K. Sudeep; V. Sai Sri Anusha; Tao Han; Buchi N. Nalluri; Diganta B. Das (AAPS PharmSciTech, 2016)

Comprehensive identification of LMW-GS genes and their protein products in a common wheat variety - Jong-Yeol Lee; Hye-Rang Beom; Susan B. Altenbach; Sun-Hyung Lim; Yeong-Tae Kim; Chon-Sik Kang; Ung-Han Yoon; Ravi Gupta; Sun-Tae Kim; Sang-Nag Ahn; Young-Mi Kim (Functional & Integrative Genomics, 2016)

Effects of 4-methylbenzylidene camphor (4-MBC) on neuronal and muscular development in zebrafish (Danio rerio) embryos - Vincent Wai Tsun Li; Mei Po Mirabelle Tsui; Xueping Chen; Michelle Nga Yu Hui; Ling Jin; Raymond H. W. Lam; Richard Man Kit Yu; Margaret B. Murphy; Jinping Cheng; Paul Kwan Sing Lam; Shuk Han Cheng (Environmental Science and Pollution Research, 2016)

First comprehensive multi-tissue transcriptome of Cherax quadricarinatus (Decapoda: Parastacidae) reveals unexpected diversity of endogenous cellulase - Mun Hua Tan; Han Ming Gan; Huan You Gan; Yin Peng Lee; Larry J. Croft; Mark B. Schultz; Adam D. Miller; Christopher M. Austin (Organisms Diversity & Evolution, 2016)

Effects of light shading and climatic conditions on the metabolic behavior of flonicamid in red bell pepper - Da-I Jung; Waziha Farha; A. M. Abd El-Aty; Sung-Woo Kim; Md. Musfiqur Rahman; Jeong-Heui Choi; Md. Humayun Kabir; So Jeong Im; Young-Jun Lee; Lieu. T. B. Truong; Ho-Chul Shin; Geon-Jae Im; et al. (Environmental Monitoring and Assessment, 2016)

Policy Implications of Allocation Methods in the Life Cycle Analysis of Integrated Corn and Corn Stover Ethanol Production - Christina E. Canter; Jennifer B. Dunn; Jeongwoo Han; Zhichao Wang; Michael Wang (BioEnergy Research, 2016)

Colored Sticky Traps to Selectively Survey Thrips in Cowpea Ecosystem - L D Tang; H Y Zhao; B L Fu; Y Han; K Liu; J H Wu (Neotropical Entomology, 2016)

Boosting BCG-primed mice with chimeric DNA vaccine HG856A induces potent multifunctional T cell responses and enhanced protection against Mycobacterium tuberculosis - Ping Ji; Zhi-Dong Hu; Han Kang; Qin Yuan; Hui Ma; Han-li Wen; Juan Wu; Zhong-Ming Li; Douglas B. Lowrie; Xiao-Yong Fan (Immunologic Research, 2016)

A novel soil manganese mechanism drives plant species loss with increased nitrogen deposition in a temperate steppe - Qiuying Tian; Nana Liu; Wenming Bai; Linghao Li; Jiquan Chen; Peter B. Reich; Qiang Yu; Dali Guo; Melinda D. Smith; Alan K. Knapp; Weixin Cheng; Peng Lu; et al. (Ecology, 2016)
Loss of plant diversity with increased anthropogenic nitrogen (N) deposition in grasslands has occurred globally. In most cases, competitive exclusion driven by preemption of light or space is invoked as a key mechanism. Here, we provide evidence from a 9‐yr N‐addition experiment for an alternative mechanism: differential sensitivity of forbs and grasses to increased soil manganese (Mn) levels. In Inner Mongolia steppes, increasing the N supply shifted plant community composition from grass–forb codominance (primarily Stipa krylovii and Artemisia frigida , respectively) to exclusive dominance by grass, with associated declines in overall species richness. Reduced abundance of forbs was linked to soil acidification that increased mobilization of soil Mn, with a 10‐fold greater accumulation of Mn in forbs than in grasses. The enhanced accumulation of Mn in forbs was correlated with reduced photosynthetic rates and growth, and is consistent with the loss of forb species. Differential accumulation of Mn between forbs and grasses can be linked to fundamental differences between dicots and monocots in the biochemical pathways regulating metal transport. These findings provide a mechanistic explanation for N‐induced species loss in temperate grasslands by linking metal mobilization in soil to differential metal acquisition and impacts on key functional groups in these ecosystems.

Scaffolding during the cell cycle by A-kinase anchoring proteins - B. Han; W. J. Poppinga; M. Schmidt (Pflügers Archiv - European Journal of Physiology, 2015)

Fate and toxic effects of environmental stressors: environmental control - Jie Zhuang; Han-Qing Yu; Theodore B. Henry; Gary S. Sayler (Ecotoxicology, 2015)

Preface: the WinMon.BE 2013 conference: steps towards an efficient and effective offshore wind farm environmental impact assessment - Steven Degraer; Jennifer Dannheim; Andrew B. Gill; Han Lindeboom; Dan Wilhelmsson (Hydrobiologia, 2015)

Offshore wind park monitoring programmes, lessons learned and recommendations for the future - Han Lindeboom; Steven Degraer; Jennifer Dannheim; Andrew B. Gill; Dan Wilhelmsson (Hydrobiologia, 2015)

QTL mapping of adult-plant resistance to stripe rust in wheat line P9897 - X. L. Zhou; D. J. Han; X. M. Chen; J. M. Mu; W. B. Xue; Q. D. Zeng; Q. L. Wang; L. L. Huang; Z. S. Kang (Euphytica, 2015)

The Fresnel–Fizeau effect and the atmospheric time delay in geodetic VLBI - S. M. Kopeikin; W.-B. Han (Journal of Geodesy, 2015)

Methods and measurement variance for field estimations of coral colony planar area using underwater photographs and semi-automated image segmentation - Benjamin P. Neal; Tsung-Han Lin; Rivah N. Winter; Tali Treibitz; Oscar Beijbom; David Kriegman; David I. Kline; B. Greg Mitchell (Environmental Monitoring and Assessment, 2015)

Discovery of a transitional host of the soybean aphid, Aphis glycines (Hemiptera: Aphididae), in northeastern China - Wenpeng Sun; Zhifeng Hu; Lanlan Han; N. B. Sanda; Yuan Hu Xuan; Kuijun Zhao (Applied Entomology and Zoology, 2015)

Biomass Storage Options Influence Net Energy and Emissions of Cellulosic Ethanol - Isaac Emery; Jennifer B. Dunn; Jeongwoo Han; Michael Wang (BioEnergy Research, 2015)

Rhizobium capsici sp. nov., isolated from root tumor of a green bell pepper (Capsicum annuum var. grossum) plant - Shih-Yao Lin; Mei-Hua Hung; Asif Hameed; You-Cheng Liu; Yi-Han Hsu; Cheng-Zhe Wen; A. B. Arun; Hans-Jürgen Busse; Stefanie P. Glaeser; Peter Kämpfer; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Effect of repeated exposures and sociality on novel food acceptance and consumption by orangutans - Madeleine E. Hardus; Adriano R. Lameira; Serge A. Wich; Han de Vries; Rachmad Wahyudi; Robert W. Shumaker; Steph B. J. Menken (Primates, 2015)

FluG affects secretion in colonies of Aspergillus niger - Fengfeng Wang; Pauline Krijgsheld; Marc Hulsman; Charissa de Bekker; Wally H. Müller; Marcel Reinders; Ronald P. de Vries; Han A. B. Wösten (Antonie van Leeuwenhoek, 2015)

VeA of Aspergillus niger increases spore dispersing capacity by impacting conidiophore architecture - Fengfeng Wang; Jan Dijksterhuis; Timon Wyatt; Han A. B. Wösten; Robert-Jan Bleichrodt (Antonie van Leeuwenhoek, 2015)

Rapid Screening of Heavy Metals and Trace Elements in Environmental Samples Using Portable X-Ray Fluorescence Spectrometer, A Comparative Study - Jacqueline Q. McComb; Christian Rogers; Fengxiang X. Han; Paul B. Tchounwou (Water, Air, & Soil Pollution, 2014)

Evaluating the causal basis of ecological success within the scleractinia: an integral projection model approach - Peter J. Edmunds; Scott C. Burgess; Hollie M. Putnam; Marissa L. Baskett; Lorenzo Bramanti; Nick S. Fabina; Xueying Han; Michael P. Lesser; Joshua S. Madin; Christopher B. Wall; Denise M. Yost; Ruth D. Gates (Marine Biology, 2014)

Health Literacy and Pap Testing in Insured Women - K. M. Mazor; A. E. Williams; D. W. Roblin; B. Gaglio; S. L. Cutrona; M. E. Costanza; P. K. J. Han; J. L. Wagner; H. Fouayzi; T. S. Field (Journal of Cancer Education, 2014)

Screening survey of co-production of fusaric acid, fusarin C, and fumonisins B1, B2 and B3 by Fusarium strains grown in maize grains - Z. Han; E. K. Tangni; B. Huybrechts; F. Munaut; J. Scauflaire; A. Wu; A. Callebaut (Mycotoxin Research, 2014)

Between-subject variability: should high be the new normal? - Hesham S. Al-Sallami; Song Lim Cheah; Shiou Yii Han; Joel Liew; Jin Lim; Mary Anne Ng; Hayneil Solanki; Run Jie Soo; Victoria Tan; Stephen B. Duffull (European Journal of Clinical Pharmacology, 2014)

Trajectory of overall health from self-report and factors contributing to health declines among cancer survivors - Jessica L. Petrick; Randi E. Foraker; Anna M. Kucharska-Newton; Bryce B. Reeve; Elizabeth A. Platz; Sally C. Stearns; Xuesong Han; B. Gwen Windham; Debra E. Irwin (Cancer Causes & Control, 2014)

Adsorption of anionic dye on magnesium hydroxide-coated pyrolytic bio-char and reuse by microwave irradiation - X. N. Zhang; G. Y. Mao; Y. B. Jiao; Y. Shang; R. P. Han (International Journal of Environmental Science and Technology, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Synthesis of water soluble copper(II) complexes: crystal structures, DNA binding, oxidative DNA cleavage, and in vitro anticancer studies - Tan Yi Han; Teoh Siang Guan; Muhammad Adnan Iqbal; Rosenani A. Haque; K. Sharmila Rajeswari; Mohamed B. Khadeer Ahamed; A. M. S. Abdul Majid (Medicinal Chemistry Research, 2014)

No fitness cost of glyphosate resistance endowed by massive EPSPS gene amplification in Amaranthus palmeri - Martin M. Vila-Aiub; Sou S. Goh; Todd A. Gaines; Heping Han; Roberto Busi; Qin Yu; Stephen B. Powles (Planta, 2014)

Two Novel Susceptibility SNPs for Ischemic Stroke Using Exome Sequencing in Chinese Han Population - Yanwei Zhang; Yeqing Tong; Yong Zhang; Hu Ding; Hao Zhang; Yijie Geng; Renli Zhang; Yuebin Ke; Jingjun Han; Zhixiang Yan; Li Zhou; Tangchun Wu; et al. (Molecular Neurobiology, 2014)

Keratinocyte growth factor and thiazolidinediones and linolenic acid differentiate characterized mammary fat pad adipose stem cells isolated from prepubertal Korean black goat to epithelial and adipogenic lineage - A. M. M. T Reza; S. Shiwani; N. K. Singh; J. D. Lohakare; S. J. Lee; D. K. Jeong; J. Y. Han; D. Rengaraj; B. W. Lee (In Vitro Cellular & Developmental Biology - Animal, 2014)

Challenge of weed risk assessment (WRA) for ecological restoration in China: The case of Rhus typhina L. and the new officially released weed risk assessment system - G. M. Wang; J. C. Yang; C. D. Jiang; G. M. Jiang; J. B. Yu; H. B. Shao; G. X. Han; Y. J. Gao (Plant Biosystems, 2013)

More breast cancer patients prefer BRCA-mutation testing without prior face-to-face genetic counseling - Aisha S. Sie; Wendy A. G. van Zelst-Stams; Liesbeth Spruijt; Arjen R. Mensenkamp; Marjolijn J. L. Ligtenberg; Han G. Brunner; Judith B. Prins; Nicoline Hoogerbrugge (Familial Cancer, 2013)

Influence of different fertilization regimes on plant-parasitic nematodes in the black soil region of Northeast China - Fengjuan Pan; Yanli Xu; Neil B. McLaughlin; Wei Liu; Xiaozeng Han; Lili Zhan; Dan Zhao (Phytoparasitica, 2013)

Heterogeneity in the mycelium: implications for the use of fungi as cell factories - Han A. B. Wösten; G. Jerre van Veluw; C. de Bekker; Pauline Krijgsheld (Biotechnology Letters, 2013)

Microsatellite markers from expressed sequence tags (ESTs) of seaweeds in differentiating various Gracilaria species - Sze-Looi Song; Phaik-Eem Lim; Siew-Moi Phang; Weng-Wah Lee; Khanjanapaj Lewmanomont; Danilo B. Largo; Nurridan Abdul Han (Journal of Applied Phycology, 2013)

Quantification of TRPV1 Protein Levels in Rat Tissues to Understand its Physiological Roles - Ping Han; Alla V. Korepanova; Melissa H. Vos; Robert B. Moreland; Mark L. Chiu; Connie R. Faltynek (Journal of Molecular Neuroscience, 2013)

Study of chloropropanols in soy sauce by gas chromatography-triple quadrupole mass spectrometry with coupled column separation without derivatisation - X.-M. Xu; H.-W. Wu; H.-L. He; B.-F. Huang; J.-L. Han; Y.-P. Ren (Food Additives & Contaminants: Part A, 2013)

Clustering of place of birth for women with breast cancer: differences by tumor characteristics - Daikwon Han; Jing Nie; Matthew R. Bonner; Christine Ambrosone; Catalin Marian; Peter Shields; Maurizio Trevisan; Stephen B. Edge; Jo L. Freudenheim (Cancer Causes & Control, 2013)

Socioecological correlates of inter-individual variation in orangutan diets at Ketambe, Sumatra - Madeleine E. Hardus; Han de Vries; David F. Dellatore; Adriano R. Lameira; Steph B. J. Menken; Serge A. Wich (Behavioral Ecology and Sociobiology, 2013)

Absence of induced resistance in Agaricus bisporus against Lecanicillium fungicola - Roeland L. Berendsen; Niek Schrier; Stefanie I. C. Kalkhove; Luis G. Lugones; Johan J. P. Baars; Carolien Zijlstra; Marjanne de Weerdt; Han A. B. Wösten; Peter A. H. M. Bakker (Antonie van Leeuwenhoek, 2013)

The blue light receptor complex WC ‐1/2 of S chizophyllum commune is involved in mushroom formation and protection against phototoxicity - Robin A. Ohm; David Aerts; Han A. B. Wösten; Luis G. Lugones (Environmental Microbiology, 2013)
Summary Blue light is necessary for initiation of mushroom formation in S chizophyllum commune . The genome of this basidiomycete contains homologues of the blue light receptor genes wc‐1 and wc‐2 of N eurospora crassa . Here, it is shown that inactivation of either or both of these genes in S . commune results in a blind phenotype. Mushroom formation was abolished in dikaryons and they formed symmetrical instead of asymmetrical colonies. Development was restored in a temperature dependent way in a Δ wc‐2 Δ wc‐2 strain by introducing a construct encompassing the wc‐2 gene under control of the promoter of the heat shock gene hsp3 . A genome‐wide expression analysis showed that the transcription factor genes c2h2 and hom1 as well as many hydrophobin genes are downregulated in light‐grown colonies of the Δ wc‐2 Δ wc‐2 mutant when compared with the wild‐type dikaryon. Inactivation of wc‐1 and/or wc‐2 also resulted in sensitivity of the mycelium to intense light. Monokaryotic mutant strains only survived exposure to 6500 lux of light by growing into the agar. Expression analysis indicates that the photosensitivity of the Δ wc‐1 and Δ wc‐2 strains is due to lower levels of photolyase and ferrochelatase.

Histidine ligand variants of a flavo-diiron protein: effects on structure and activities - Han Fang; Jonathan D. Caranto; Rosalinda Mendoza; Alexander B. Taylor; P. John Hart; Donald M. Kurtz (JBIC Journal of Biological Inorganic Chemistry, 2012)

Energy consumption and greenhouse gas emissions from enzyme and yeast manufacture for corn and cellulosic ethanol production - Jennifer B. Dunn; Steffen Mueller; Michael Wang; Jeongwoo Han (Biotechnology Letters, 2012)

Water Maze Spatial Learning Enhances Social Recognition Ability in Aged Rats - Q. Zeng; J. Han; B. Wang; Sh. An; Y. Duan; S. Dong; J. Ma; L. Yang; X. Cao (Neurophysiology, 2012)

Co-expression of soybean Dicer-like genes in response to stress and development - Shaun J. Curtin; Michael B. Kantar; Han W. Yoon; Adam M. Whaley; Jessica A. Schlueter; Robert M. Stupar (Functional & Integrative Genomics, 2012)

Effective communication of uncertainty in the IPCC reports - David V. Budescu; Han-Hui Por; Stephen B. Broomell (Climatic Change, 2012)

Isolation, mapping, SNP detection and association with backfat traits of the porcine CTNNBL1 and DGAT2 genes - Q. Yin; H. -W. Yang; X. -L. Han; B. Fan; B. Liu (Molecular Biology Reports, 2012)

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Use of total precipitable water classification of a priori error and quality control in atmospheric temperature and water vapor sounding retrieval - Eun-Han Kwon; Jun Li; Jinlong Li; B. J. Sohn; Elisabeth Weisz (Advances in Atmospheric Sciences, 2012)

Genomic sequence of infectious hypodermal and hematopoietic necrosis virus (IHHNV) KLV-2010-01 originating from the first Korean outbreak in cultured Litopenaeus vannamei - J. H. Kim; H. K. Kim; V. G. Nguyen; B. K. Park; C. H. Choresca; S. P. Shin; J. E. Han; J. W. Jun; S. C. Park (Archives of Virology, 2012)

5-Phenylselenyl- and 5-methylselenyl-methyl-2′-deoxyuridine induce oxidative stress, DNA damage, and caspase-2-dependent apoptosis in cancer cells - Byeong Mo Kim; Ambadas B. Rode; Eun Jong Han; In Seok Hong; Sung Hee Hong (Apoptosis, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Translocation and oligomerization of Bax is regulated independently by activation of p38 MAPK and caspase-2 during MN9D dopaminergic neurodegeneration - Chang-Ki Oh; Baek-Soo Han; Won-Seok Choi; Moussa B. H. Youdim; Young J. Oh (Apoptosis, 2011)

Prevalence and different characteristics of two serotypes of Streptococcus parauberis isolated from the farmed olive flounder, Paralichthys olivaceus (Temminck and Schlegel), in Korea - S Y Han; B K Kang; B J Kang; S P Shin; B H Soen; J M Kim; J H Kim; C H Choresca; J E Han; J W Jun; S C Park (Journal of Fish Diseases, 2011)
The prevalence of two serotypes of Streptococcus parauberis isolated from the olive flounder, Paralichthys olivaceus , was evaluated in a total of 29 isolates between 2003 and 2010 in Korea. Streptococcus parauberis isolates were divided into two serologically distinct types (serotype 1 and serotype 2), except for one strain (S1091), using an agglutination assay with rabbit antiserum, and serotype 1 was identified as the dominant type (24 of 29 isolates) in this study. To identify the characteristics of the two serotypes of S. parauberis , we conducted a biochemical test using the API 20 Strep kit, a transmission electron microscopy (TEM) assay, sequence analysis of 16S‐23S rRNA intergenic spacer region (ISR) and a pathogenicity test. In TEM, both serotypes possessed polysaccharide capsule layers around the cell surface when bacterial cells were treated with a homologous serotype of rabbit antiserum. However, we were unable to discriminate serotype‐specific biochemical characteristics and genetic characteristics of 16S‐23S rRNA ISR between the two serotypes. In the pathogenicity test, the serotype 1 strains induced significantly higher mortality than the serotype 2 strains in olive flounder when experimentally inoculated via the intraperitoneal route.

Species-level correlates of susceptibility to the pathogenic amphibian fungus Batrachochytrium dendrobatidis in the United States - Betsy A. Bancroft; Barbara A. Han; Catherine L. Searle; Lindsay M. Biga; Deanna H. Olson; Lee B. Kats; Joshua J. Lawler; Andrew R. Blaustein (Biodiversity and Conservation, 2011)

Absence of repellents in Ustilago maydis induces genes encoding small secreted proteins - Wieke R. Teertstra; Pauline Krijgsheld; Han A. B. Wösten (Antonie van Leeuwenhoek, 2011)

ASIP genetic variants and the number of non-melanoma skin cancers - Wen Lin; Abrar A. Qureshi; Peter Kraft; Hongmei Nan; Qun Guo; Frank B. Hu; Majken K. Jensen; Jiali Han (Cancer Causes & Control, 2011)

Heterogenic expression of genes encoding secreted proteins at the periphery of Aspergillus niger colonies - Arman Vinck; Charissa de Bekker; Adam Ossin; Robin A. Ohm; Ronald P. de Vries; Han A. B. Wösten (Environmental Microbiology, 2011)
Summary Colonization of a substrate by fungi starts with the invasion of exploring hyphae. These hyphae secrete enzymes that degrade the organic material into small molecules that can be taken up by the fungus to serve as nutrients. We previously showed that only part of the exploring hyphae of Aspergillus niger highly express the glucoamylase gene glaA . This was an unexpected finding since all exploring hyphae are exposed to the same environmental conditions. Using GFP as a reporter, we here demonstrate that the acid amylase gene aamA , the α‐glucuronidase gene aguA , and the feruloyl esterase gene faeA of A. niger are also subject to heterogenic expression within the exploring mycelium. Coexpression studies using GFP and dTomato as reporters showed that hyphae that highly express one of these genes also highly express the other genes encoding secreted proteins. Moreover, these hyphae also highly express the amylolytic regulatory gene amyR , and the glyceraldehyde‐3‐phosphate dehydrogenase gene gpdA. In situ hybridization demonstrated that the high expressers are characterized by a high 18S rRNA content. Taken together, it is concluded that two subpopulations of hyphae can be distinguished within the exploring mycelium of A. niger . The experimental data indicate that these subpopulations differ in their transcriptional and translational activity.

One centimeter-level observations of diurnal ocean tides from global monthly mean time-variable gravity fields - Shin-Chan Han; Richard D. Ray; Scott B. Luthcke (Journal of Geodesy, 2010)

An efficient gene deletion procedure for the mushroom-forming basidiomycete Schizophyllum commune - Robin A. Ohm; Jan F. de Jong; Elsa Berends; Fengfeng Wang; Han A. B. Wösten; Luis G. Lugones (World Journal of Microbiology and Biotechnology, 2010)

Determination of Imazaquin and its Metabolite by Liquid Chromatography-Quadrupole-Time of Flight Tandem Mass - H. B. Yao; G. J. Han; G. X. Liu; Y. Xie; C. H. Wang (Bulletin of Environmental Contamination and Toxicology, 2010)

Does larval duration contribute to population genetic isolation of the Japanese eel Anguilla japonica ? - Y. S. HAN; C. L. HUNG; Y. IIZUKA; H. C. CHANG; B. J. CHANG; H. C. HO; J. C. SHIAO (Fisheries Management and Ecology, 2010)

Molecular Characterisation of the Faecal Microbiota in Patients with Type II Diabetes - Xiaokang Wu; Chaofeng Ma; Lei Han; Muhammad Nawaz; Fei Gao; Xuyan Zhang; Pengbo Yu; Chang’an Zhao; Lianchuan Li; Aiping Zhou; Juan Wang; John E. Moore; et al. (Current Microbiology, 2010)

Female BRCA mutation carriers with a preference for prophylactic mastectomy are more likely to participate an educational-support group and to proceed with the preferred intervention within 2 years - Karin M. Landsbergen; Judith B. Prins; Yvonne J. L. Kamm; Han G. Brunner; Nicoline Hoogerbrugge (Familial Cancer, 2010)

Population structure of the olive flounder ( Paralichthys olivaceus ) in Korea inferred from microsatellite marker analysis - W.‐J. Kim; K.‐K. Kim; H.‐S. Han; B.‐H. Nam; Y.‐O. Kim; H.‐J. Kong; J.‐K. Noh; M. Yoon (Journal of Fish Biology, 2010)
The population structure of olive flounder Paralichthys olivaceus was estimated using nine polymorphic microsatellite (MS) loci in 459 individuals collected from eight populations, including five wild and three hatchery populations in Korea. Genetic variation in hatchery (mean number of alleles per locus, A = 10·2–12·1; allelic richness, A R = 9·3–10·1; observed heterozygosity, H O = 0·766–0·805) and wild (mean number of alleles per locus, A = 11·8–19·6; allelic richness, A R = 10·9–16·1; observed heterozygosity, H O = 0·820–0·888) samples did not differ significantly, suggesting a sufficient level of genetic variation in these well‐managed hatchery populations, which have not lost a substantial amount of genetic diversity. Neighbour‐joining tree and principal component analyses showed that genetic separation between eastern and pooled western and southern wild populations in Korea was probably influenced by restricted gene flow between regional populations due to the barrier effects of sea currents. The pooled western and southern populations are genetically close, perhaps because larval dispersal may depend on warm currents. One wild population (sample from Wando) was genetically divergent from the main distribution, but it was genetically close to hatchery populations, indicating that the genetic composition of the studied populations may be affected by hydrographic conditions and the release of fish stocks. The estimated genetic population structure and potential applications of MS markers may aid in the proper management of P. olivaceus populations.

Comparison of reproductive development in triploid and diploid female rainbow trout Oncorhynchus mykiss - Y. Han; M. Liu; L. Lan Zhang; B. Simpson; G. Xue Zhang (Journal of Fish Biology, 2010)
The diploid rainbow trout Oncorhynchus mykiss reached sexual maturity 3 years after hatching and its oogenesis underwent four stages, which were oogonia, primary oocyte, secondary oocyte and egg. Reproductive development and hormone changes of 4 to 35 month‐old female O. mykiss were investigated using histological and radioimmunoassay methods in order to provide a theoretical and practical basis for the use of triploid female O. mykiss . The oogonium of the triploid female could develop into the oocytes of the prophase with abortion occurring later; the oogonium was surrounded by stroma cells to form the oogonium cluster and the gonads showed a virilescent tendency when the oogonium clusters were gradually replaced by spermatogenic‐like cytocysts. After 13 months, amounts of gonadotropic hormone (GtH‐I, GtH‐II) and oestradiol (17 β ‐E 2 ) in triploid females were lower than in diploid fish at corresponding time periods, but the amounts of testosterone (T) increased consistently after 21 months and were more than in diploid fish in the corresponding time periods ( P > 0·05). The infertility of triploid females resulted from meiosis failure, which caused developmental abortion of oocytes and oogonium formed cytocysts before the prophase oocytes. The cytocyst formation was due to the lack of the normal interaction of ovum and follicular cells, the development of follicular cells producing steroids were inhibited, the arylate path from T to 17 β ‐E 2 was interrupted, concentration of 17 β ‐E 2 decreased and concentration of T increased in the blood, the content of vitellogenin (Vg) decreased in the liver with a low 17 β ‐E 2 and high T caused to ovaries to show a tendency to be virilescent.

Landscape‐scale analyses suggest both nutrient and antipredator advantages to Serengeti herbivore hotspots - T. Michael Anderson; J. Grant C. Hopcraft; Stephanie Eby; Mark Ritchie; James B. Grace; Han Olff (Ecology, 2010)
Mechanistic explanations of herbivore spatial distribution have focused largely on either resource‐related (bottom‐up) or predation‐related (top‐down) factors. We studied direct and indirect influences on the spatial distributions of Serengeti herbivore hotspots, defined as temporally stable areas inhabited by mixed herds of resident grazers. Remote sensing and variation in landscape features were first used to create a map of the spatial distribution of hotspots, which was tested for accuracy against an independent data set of herbivore observations. Subsequently, we applied structural equation modeling to data on soil fertility and plant quality and quantity across a range of sites. We found that hotspots in Serengeti occur in areas that are relatively flat and located away from rivers, sites where ungulates are less susceptible to predation. Further, hotspots tend to occur in areas where hydrology and rainfall create conditions of relatively low‐standing plant biomass, which, coupled with grazing, increases forage quality while decreasing predation risk. Low‐standing biomass and higher leaf concentrations of N, Na, and Mg were strong direct predictors of hotspot occurrence. Soil fertility had indirect effects on hotspot occurrence by promoting leaf Na and Mg. The results indicate that landscape features contribute in direct and indirect ways to influence the spatial distribution of hotspots and that the best models incorporated both resource‐ and predation‐related factors. Our study highlights the collective and simultaneous role of bottom‐up and top‐down factors in determining ungulate spatial distributions.

The septal pore cap is an organelle that functions in vegetative growth and mushroom formation of the wood‐rot fungus Schizophyllum commune - Arend F. Van Peer; Fengfeng Wang; Kenneth G. A. Van Driel; Jan F. De Jong; Elly G. Van Donselaar; Wally H. Müller; Teun Boekhout; Luis G. Lugones; Han A. B. Wösten (Environmental Microbiology, 2010)
Summary Mushroom‐forming basidiomycetes colonize large areas in nature. Their hyphae are compartmentalized by perforated septa, which are usually covered by a septal pore cap (SPC). Here, we describe, for the first time, the composition and function of SPCs using the model system Schizophyllum commune . The SPC of S. commune was shown to consist of a proteinaceous matrix covered by a lipid membrane. The matrix was demonstrated to define the ultrastructure of the SPC and to consist of two main proteins, Spc14 and Spc33. Gene spc14 encodes a protein of 86 amino acids, which lacks known domain, signal or localization sequences. Gene spc33 encodes a 239 and a 340 amino acid variant. Both forms contain a predicted signal anchor that targets them to the ER. Immuno‐localization showed the presence of Spc33 in the SPC but not in ER. From this and previous reports it is concluded that the SPC is derived from this organelle. Inactivation of spc33 resulted in loss of SPCs and the inability to close septa. The latter may well explain why vegetative growth and mushroom formation were severely reduced in strains in which spc33 was inactivated.

A novel single-nucleotide polymorphism of thevisfatin gene and its associations with performance traits in the chicken - R. L. Han; X. Y. Lan; L. Z. Zhang; G. Ren; Y. J. Jing; M. J. Li; B. Zhang; M. Zhao; Y. K. Guo; X. T. Kang; H. Chen (Journal of Applied Genetics, 2010)

Genetic testing for Lynch syndrome in the first year of colorectal cancer: a review of the psychological impact - Karin M. Landsbergen; Judith B. Prins; Han G. Brunner; Floris W. Kraaimaat; Nicoline Hoogerbrugge (Familial Cancer, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

Paraquat resistance in a Lolium rigidum population is governed by one major nuclear gene - Qin Yu; Heping Han; Linh Nguyen; John W. Forster; Stephen B. Powles (Theoretical and Applied Genetics, 2009)

Two glucuronoyl esterases of Phanerochaete chrysosporium - Miroslava Ďuranová; Silvia Špániková; Han A. B. Wösten; Peter Biely; Ronald P. de Vries (Archives of Microbiology, 2009)

Estimation of the gross primary production of an old‐growth temperate mixed forest using eddy covariance and remote sensing - J. B. Wu; X. M. Xiao; D. X. Guan; T. T. Shi; C. J. Jin; S. J. Han (International Journal of Remote Sensing, 2009)

Extractability and Bioavailability of Mercury from a Mercury Sulfide Contaminated Soil in Oak Ridge, Tennessee, USA - Fengxiang X. Han; Safwan Shiyab; Jian Chen; Yi Su; David L. Monts; Charles A. Waggoner; Frank B. Matta (Water, Air, & Soil Pollution, 2008)

Sources and Properties of Natural Organic Matter (NOM) in Water Along the Dongjiang River (the Source of Hong Kong’s Drinking Water) and Toxicological Assay of Its Chlorination By-Products - Y. Liang; H. C. Hong; L. H. Dong; C. Y. Lan; B. P. Han; M. H. Wong (Archives of Environmental Contamination and Toxicology, 2008)

Control and possible applications of a novel carrot-spoilage basidiomycete, Fibulorhizoctonia psychrophila - Ronald P. de Vries; Elvira S. de Lange; Han A. B. Wösten; Joost A. Stalpers (Antonie van Leeuwenhoek, 2008)

Characterization of a Homogentisate Dioxygenase Mutant in Pseudomonas chlororaphis O6 - B. R. Kang; S. H. Han; S. M. Cho; A. J. Anderson; I. S. Kim; S. K. Park; Y. C. Kim (Current Microbiology, 2008)

Exposure to traffic emissions throughout life and risk of breast cancer: the Western New York Exposures and Breast Cancer (WEB) study - Jing Nie; Jan Beyea; Matthew R. Bonner; Daikwon Han; John E. Vena; Peter Rogerson; Dominica Vito; Paola Muti; Maurizio Trevisan; Stephen B. Edge; Jo L. Freudenheim (Cancer Causes & Control, 2007)

A novel gene, Pi40(t), linked to the DNA markers derived from NBS-LRR motifs confers broad spectrum of blast resistance in rice - J. U. Jeung; B. R. Kim; Y. C. Cho; S. S. Han; H. P. Moon; Y. T. Lee; K. K. Jena (Theoretical and Applied Genetics, 2007)

Changes of chemical and nutrient composition of porcine blood during fermentation by Aspergillus oryzae - J. Z. Wang; M. Zhang; F. Z. Ren; B. Z. Han; L. Wang; S. W. Chen; A. Humera (World Journal of Microbiology and Biotechnology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Intragenic deletion in the LARGE gene causes Walker-Warburg syndrome - Jeroen van Reeuwijk; Prabhjit K. Grewal; Mustafa A. M. Salih; Daniel Beltrán-Valero de Bernabé; Jenny M. McLaughlan; Caroline B. Michielse; Ralf Herrmann; Jane E. Hewitt; Alice Steinbrecher; Mohamed Z. Seidahmed; Mohamed M. Shaheed; Abdullah Abomelha; et al. (Human Genetics, 2007)

Regulation of Antioxidants and Phase 2 Enzymes by Shear-Induced Reactive Oxygen Species in Endothelial Cells - Charles I. Jones; Hong Zhu; Sergio F. Martin; Zhaosheng Han; Yunbo Li; B. Rita Alevriadou (Annals of Biomedical Engineering, 2007)

Spectral reflectance and leaf internal structure changes of barley plants due to phytoextraction of zinc and cadmium - B. B. Maruthi Sridhar; F. X. Han; S. V. Diehl; D. L. Monts; Y. Su (International Journal of Remote Sensing, 2007)

Monitoring the effects of arsenic and chromium accumulation in Chinese brake fern ( Pteris vittata ) - Maruthi B. B. Sridhar; F. X. Han; S. V. Diehl; D. L. Monts; Y. Su (International Journal of Remote Sensing, 2007)

Effect of Bioaccumulation of Cs and Sr Natural Isotopes on Foliar Structure and Plant Spectral Reflectance of Indian Mustard (Brassica Juncea) - Yi Su; B. B. Maruthi Sridhar; F. X. Han; S. V. Diehl; D. L. Monts (Water, Air, & Soil Pollution, 2007)

Volume density and distribution of mitochondria in harbor seal (Phoca vitulina) skeletal muscle - Rebecca R. Watson; Shane B. Kanatous; Daniel F. Cowan; Julie W. Wen; Violet C. Han; Randall W. Davis (Journal of Comparative Physiology B, 2006)

Removal of Alachlor and Pretilachlor by Laboratory-Synthesized Zerovalent Iron in Pesticide Formulation Solution - H. Y. Kim; I. K. Kim; J. H. Shim; Y.-C. Kim; T.-H. Han; K.-C. Chung; P. I. Kim; B.-T. Oh; I. S. Kim (Bulletin of Environmental Contamination and Toxicology, 2006)

Seed-specific expression of sesame microsomal oleic acid desaturase is controlled by combinatorial properties between negative cis-regulatory elements in the SeFAD2 promoter and enhancers in the 5′-UTR intron - Mi Jung Kim; Heeja Kim; Jeong Sheop Shin; Chung-Han Chung; John B. Ohlrogge; Mi Chung Suh (Molecular Genetics and Genomics, 2006)

Extent and pattern of DNA methylation alteration in rice lines derived from introgressive hybridization of rice and Zizania latifolia Griseb - Z. Y. Dong; Y. M. Wang; Z. J. Zhang; Y. Shen; X. Y. Lin; X. F. Ou; F. P. Han; B. Liu (Theoretical and Applied Genetics, 2006)

Rapid Determination of Mercury in Plant and Soil Samples Using Inductively Coupled Plasma Atomic Emission Spectroscopy, a Comparative Study - Fengxiang X. Han; W. Dean Patterson; Yunju Xia; B. B. Maruthi Sridhar; Yi Su (Water, Air, & Soil Pollution, 2006)

The influence of muscle type and dystrophin deficiency on murine expression profiles - Judith N. Haslett; Peter B. Kang; Mei Han; Alvin T. Kho; Despina Sanoudou; Jay M. Volinski; Alan H. Beggs; Isaac S. Kohane; Louis M. Kunkel (Mammalian Genome, 2005)

Seasonal Variation of Chemical Composition in Fine Particles at Gosan, Korea - J. S. Han; K. J. Moon; B. J. Kong; S. J. Lee; J. E. Kim; Y. J. Kim (Environmental Monitoring and Assessment, 2005)

Secondhand smoke exposure in early life and the risk of breast cancer among never smokers (United States) - Matthew R. Bonner; Jing Nie; Daikwon Han; John E. Vena; Peter Rogerson; Paola Muti; Maurizio Trevisan; Stephen B. Edge; Jo L. Freudenheim (Cancer Causes & Control, 2005)

Inhibiting the Sexual Behavior of Female Cotton Bollworm Helicoverpa armigera - W. X. Dong; B. Y. Han; J. W. Du (Journal of Insect Behavior, 2005)

Effects of Acid Precipitation and Aluminum on Carbohydrate Metabolism in Mycorrhizae of Pinus massioniana - J. K. Tan; F. X. Kong; H. S. Cao; Y. Yu; X. B. Han (Bulletin of Environmental Contamination and Toxicology, 2005)

Time Course Biochemical Responses of Green Algae Scenedesmus obliquus to Aluminum and Low pH - S. A. Jusu; F. X. Kong; B. Q. Qing; J. K. Tan; X. B. Han (Bulletin of Environmental Contamination and Toxicology, 2004)

Geographic clustering of residence in early life and subsequent risk of breast cancer (United States) - Daikwon Han; Peter A. Rogerson; Jing Nie; Matthew R. Bonner; John E. Vena; Dominica Vito; Paola Muti; Maurizio Trevisan; Stephen B. Edge; Jo L. Freudenheim (Cancer Causes & Control, 2004)

Fine mapping of a malting-quality QTL complex near the chromosome 4H S telomere in barley - W. Gao; J. A. Clancy; F. Han; B. L. Jones; A. Budde; D. M. Wesenberg; A. Kleinhofs; S. E. Ullrich (Theoretical and Applied Genetics, 2004)

Distribution, transformation and bioavailability of trivalent and hexavalent chromium in contaminated soil - Fengxiang X. Han; Yi Su; B. B. Maruthi Sridhar; David L. Monts (Plant and Soil, 2004)

Arsenic Accumulation and Acute Toxicity in Aquacultural Juvenile Milkfish ( Chanos chanos ) from Blackfoot Disease Area in Taiwan - M.-C. Lin; H.-H. Cheng; H.-Y. Lin; Y.-C. Chen; Y.-P. Chen; G.-P. Chang-Chien; Y.-H. Chou; C.-M. Liao; C.-F. Dai; B.-C. Han; C.-W. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Some technical aspects of magnetic stimulation coil design with the ferromagnetic effect - B. H. Han; S. Y. Lee; J. H. Kim; J. H. Yi (Medical & Biological Engineering & Computing, 2003)

Comparative analysis of expressed sequence tags from Sesamum indicum and Arabidopsis thaliana developing seeds - Mi Chung Suh; Mi Jung Kim; Cheol-Goo Hur; Jung Myung Bae; Young In Park; Chung-Han Chung; Churl-Whan Kang; John B. Ohlrogge (Plant Molecular Biology, 2003)

Effects of fish introduction on the length of the tail of cryptomonads in mesocosm experiments - B. H. Kim; M.-S. Han; N. Takamura (Oecologia, 2003)

Structure prediction for the di-heme cytochrome b 561 protein family - Denys Bashtovyy; Alajos Brczi; Han Asard; Tibor Pli (Protoplasma, 2003)

River Flow Modelling Using Fuzzy Decision Trees - D. Han; I. D. Cluckie; D. Karbassioun; J. Lawry; B. Krauskopf (Water Resources Management, 2002)

Perturbations of Population Growth in a Microcosm by Industrial Metal Plating and Ice Cream Mills Wastewater and Landfill Leachate - S.-U. Wui; K. Cho; Y. Inamori; J.-S. Lee; M.-S. Han; J.-B. Lee (Bulletin of Environmental Contamination and Toxicology, 2002)

Cadmium-Induced Apoptosis in H9c2, A7r5, and C6-Glial Cell - M. K. Choi; B. H. Kim; Y. Y. Chung; M. S. Han (Bulletin of Environmental Contamination and Toxicology, 2002)

Differential distribution of interneurons in the neural networks that control walking in the mudpuppy (Necturus maculatus) spinal cord - J. Cheng; K. Jovanovic; Y. Aoyagi; D. J. Bennett; Y. Han; R. B. Stein (Experimental Brain Research, 2002)

FURTHER CHARACTERIZATION OF BC3H1 MYOGENIC CELLS REVEALS LACK OF P53 ACTIVITY AND UNDEREXPRESSION OF SEVERAL P53 REGULATED AND EXTRACELLULAR MATRIX–ASSOCIATED GENE PRODUCTS - SANDRA B. SHARP; MARIA VILLALVAZO; MICKEY HUANG; RODOLFO GONZALEZ; IRANIA ALARCON; MATTHEW BAHAMONDE; DIANE M. D'AGOSTIN; SAGAR DAMLE; ALEX ESPINOSA; SEOG J. HAN; JESSICA LIU; PAULA NAVARRO; et al. (In Vitro Cellular & Developmental Biology - Animal, 2002)

Origin of laminated diatom ooze in King George Basin sediments from Bransfield Strait, Antarctica - H. I. Yoon; B. K. Park; M. W. Han; B. K. Khim; Y. Kim; C. Y. Kang (Geosciences Journal, 2001)

Physical and Chemical Properties of a Winter-Time Yellow Sand Event in Northeast Asia - B. G. Kim; J. Y. Ahn; H. R. Noh; C. J. Park; J. S. Han; S. U. Park (Water, Air, & Soil Pollution, 2001)

Higher-plant plasma membrane cytochromeb 561: A protein in search of a function - Han Asard; Jyoti Kapila; Wim Verelst; Alajos Brczi (Protoplasma, 2001)

Physical mapping of the barley stem rust resistance gene rpg4 - A. Druka; D. Kudrna; F. Han; A. Kilian; B. Steffenson; D. Frisch; J. Tomkins; R. Wing; A. Kleinhofs (Molecular Genetics and Genomics, 2000)

An integrated genetic map of Populus deltoides based on amplified fragment length polymorphisms - R. L. Wu; Y. F. Han; J. J. Hu; J. J. Fang; L. Li; M. L. Li; Z. -B. Zeng (Theoretical and Applied Genetics, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

Roles of cyclin D1 and related genes in growth inhibition, senescence and apoptosis - E. K.-H. Han; S.-C. Ng; N. Arber; M. Begemann; I. B. Weinstein (Apoptosis, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Refined mapping of the gene for autosomal dominant retinitis pigmentosa (RP17) on chromosome 17q22 - A. I. den Hollander; S. D. van der Velde-Visser; Alfred J. L. G. Pinckers; Carel B. Hoyng; Han G. Brunner; Frans P. M. Cremers (Human Genetics, 1999)

Estimation of Target Hazard Quotients and Potential Health Risks for Metals by Consumption of Seafood in Taiwan - B.-C. Han; W. L. Jeng; R. Y. Chen; G. T. Fang; T. C. Hung; R. J. Tseng (Archives of Environmental Contamination and Toxicology, 1998)

Response of The Lacewing Chrysopa cognata to Pheromones of its Aphid Prey - K. S. Boo; I. B. Chung; K. S. Han; J. A. Pickett; L. J. Wadhams (Journal of Chemical Ecology, 1998)

A comparative molecular analysis of four rat smooth muscle cell lines - Anthony B. Firulli; David Han; Louise Kelly-Roloff; Victor E. Koteliansky; Stephen M. Schwartz; Eric N. Olson; Joseph M. Miano (In Vitro Cellular & Developmental Biology - Animal, 1998)

Strategies for the improvement of salidroside production in cell suspension cultures of Rhodiola sachalinensis - J. F. Xu; C. B. Liu; A. M. Han; P. S. Feng; Z. G. Su (Plant Cell Reports, 1998)

Rock-Shells ( Thais clavigera ) as an Indicator of As, Cu, and Zn Contamination on the Putai Coast of the Black-Foot Disease Area in Taiwan - B. C. Han; W. L. Jeng; M. S. Jeng; L. T. Kao; P. J. Meng; Y. L. Huang (Archives of Environmental Contamination and Toxicology, 1997)

Fine structure mapping of the barley chromosome-1 centromere region containing malting-quality QTLs - F. Han; S. E. Ullrich; A. Kleinhofs; B. L. Jones; P. M. Hayes; D. M. Wesenberg (Theoretical and Applied Genetics, 1997)

Towards map-based cloning of the barley stem rust resistance genes Rpg1 and rpg4 using rice as an intergenomic cloning vehicle - A. Kilian; J. Chen; F. Han; B. Steffenson; A. Kleinhofs (Plant Molecular Biology, 1997)

Chirp (2–7 kHz) echo characters in the Ulleung Basin - S. K. Chough; S. H. Lee; J. W. Kim; S. C. Park; D. G. Yoo; H. S. Han; S. H. Yoon; S. B. Oh; Y. B. Kim; G. G. Back (Geosciences Journal, 1997)

Effect of EHS matrix on expression of transgenes in HC11 cells - T. H. Lee; M. G. Baik; W. B. Im; C. S. Lee; Y. M. Han; S. J. Kim; K. K. Lee; Y. J. Choi (In Vitro Cellular & Developmental Biology - Animal, 1997)

Monitoring lead pollution near a storage battery recycling plant in Taiwan, Republic of China - C. -Y. Yeh; H. -Y. Chiou; R. -Y. Chen; K. -H. Yeh; W. -L. Jeng; B. -C. Han (Archives of Environmental Contamination and Toxicology, 1996)

Monitoring Lead Pollution Near a Storage Battery Recycling Plant in Taiwan, Republic of China - C.-Y. Yeh; H.-Y. Chiou; R.-Y. Chen; K.-H. Yeh; W.-L. Jeng, B.-C. Han (Archives of Environmental Contamination and Toxicology, 1996)

Insoluble hydrophobin complexes in the walls of Schizophyllum commune and other filamentous fungi - Onno M. H. de Vries; M. Peter Fekkes; Han A. B. Wösten; Joseph G. H. Wessels (Archives of Microbiology, 1993)

Mirex in human milk in upstate New York - B. Bush; J. Snow; S. Connor; L. Rueckert; Y. Han; P. Dymerski; D. Hilker (Archives of Environmental Contamination and Toxicology, 1983)

Regulation of amidase formation in mutants from Pseudomonas aeruginosa PAO lacking glutamine synthetase activity - Dick B. Janssen; Patricia M. Herst; Han M. L. J. Joosten; Chris van der Drift (Archives of Microbiology, 1982)

Nitrogen control in Pseudomonas aeruginosa: A role for glutamine in the regulation of the synthesis of NADP-dependent glutamate dehydrogenase, urease and histidase - Dick B. Janssen; Patricia M. Herst; Han M. L. J. Joosten; Chris van der Drift (Archives of Microbiology, 1981)